Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

Low-temperature pyrolysis enhanced dissociation and waste oil assisted green flotation for the recovery of electrode materials from spent LiCoO2 batteries - Xin-long Li; Xiang-nan Zhu; Guang-liang Wei; Chun-liu Hu; Xiao-tian Zhao; Jing-tao Chen; Wen-hao Gao; Chun-chen Nie; Yong-qiang Zhao; Gu-yue Li (Minerals Engineering, 2026)

Sesquiterpenoids isolated from the leaves of Aucklandia costus and their inhibitory effect on nitric oxide production - Long-Gao Xiao; Tao-Bin He; Yan-Xi Li; Yun Niu; Huan Yan; Hui-Ying Liu; Hui Liu; Wei Ni; Xin Fang; Hai-Yang Liu (Phytochemistry, 2026)

Self-healing materials for food packaging: Design principles, activation mechanisms and implications for food safety - Mengzi Nie; Runkang Qiu; Huihui Yang; Xiangyu Liang; Ziqian Li; Long Li; Bei Fan; Li-Tao Tong; Peihua Ma; Fengzhong Wang (Food Research International, 2026)

Microwave coupled ultrasound pretreatment for enhancing acid leaching of ilmenite and its mechanism - Rui Liu; Long Xiang; Tao Long; Wenrong Xiang; Jiahao Hu; Li Li; Chunhui Han; Xingran Zhang (Minerals Engineering, 2026)

Vortex bionic structural composites fabricated by DLP 3D printing with high electromagnetic shielding effect and thermal conductive property - Jingxing Gui; Tao Zhang; Sha Long; Yingtao Li; Feiyue Zhou; Yuxuan Ma; Yuting Xue; Xueting Xu; Chunyan Hu; Baojiang Liu; Dan Yu; Wei Wang (Chemical Engineering Journal, 2026)

Corrigendum to “DNA methylation mediates the association between organochlorine pesticides and MASLD: An epigenome-wide association study with integrated AOP framework” [J Hazard Mater, 507 (2026) 141727] - Yi Guo; Yutong You; Xin Guan; Yu Yin; Zhen Yin; Guorong Zhong; Chengyong Jia; Yuying Wen; Wenhui Li; Hui Zhao; Shengli Chen; Xi Wang; et al. (Journal of Hazardous Materials, 2026)

Operationalizing the serviceshed concept to enhance the effectiveness and equity of flood regulation services in systematic conservation planning - Xue Ding; Jun-Long Huang; Yu Tao; Jiman Li; Henghui Xi; Weixin Ou (Environmental Impact Assessment Review, 2026)

Spin-polarized plasmonic perovskites for magnetic-field-enhanced photocatalytic styrene oxidation - Linqian Li; Qiang Su; Xuesen Li; Qiang Luo; Jiale Pu; Long Chen; Yongjie Yang; Tao Liu; Ning Wang (Chemical Engineering Journal, 2026)

Concentration-dependent variation in carbon allocation and microbial assembly in chain elongation microbiota: Comparative effects of acetate, ethanol, and lactate - Ya-Ning Song; Li-Juan Chai; Ling Ao; Jun-Lan Mei; Yu-Long Li; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Bioresource Technology, 2026)

A dynamic point-association graph method for surface settlement prediction in subway foundation pits: application to Daqiao Station - Tao Kong; Zhen-hua Yang; Qing Tan; Zhao-cheng Liu; Ke Liu; Chuan-dong Yao; Zhen-long Xue; Yu-heng Li (Applied Geophysics, 2026)

A nonlinear creep damage model for deep buried schist considering water content-stress-time coupling effects - Lei She; Xin-yang Hu; Li-feng Wen; Yan-long Li; Cheng-cheng Hu; Wen-jie Liu; Jun-tao Yan (Transportation Geotechnics, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

A multi-AI framework for accurate characterization of preferential flow pathways using a field tracer experiment - Yanhao Wu; Haijian Xie; Mengcheng Zhang; Jiayi Hong; Mei Li; Jinzhong Wan; Tao Long; Shengtian Zhang (Journal of Hydrology, 2026)

Preferentially selective lithium recovery from spent lithium-ion battery leachates using NaBPh4/TBP synergistic extraction - Qian Cheng; Yue Wang; Yongxiang Wang; Panfeng Gao; Jun-Tao Li; Jiangxue Long; Haiyan Fu (Hydrometallurgy, 2026)

Bioactivity assay coupled with molecular networking for the discovery of antioxidants from purslane - Yan-Xi Li; Mei-Ru Wang; Long-Gao Xiao; Huan Yan; Shan-Shan Ling; Hui Liu; Tao-Bin He; Wei Ni; Xin Fang; Hai-Yang Liu (Food Research International, 2026)

Effects of Dietary Macleaya cordata Extract on Growth Performance, Antioxidant Capacity, Immunity, and Stress Resistance in Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Fan-Le Jia; Yao-Peng Lu; Ze-Long Zhang; Xiu-Xia Zhang; Pei-Hua Zheng; Jun-Tao Li; Ying-Hui Liang; Dan Mu; Jian-An Xian (Fishes, 2026)
High-density, intensive aquaculture has led to the deterioration of the aquatic environment, which compromises the survival, immune function and disease resistance of aquatic animals. This study investigated the effects of dietary supplementation with different levels of Macleaya cordata extract (MCE) on growth performance, muscle composition, antioxidant capacity, immune function, and stress resistance in red claw crayfish (Cherax quadricarinatus). Juvenile crayfish with an initial body weight of 0.22 ± 0.02 g were fed diets supplemented with 0 (Diet 1, Control), 0.01 (Diet 2), 0.02 (Diet 3), 0.04 (Diet 4), 0.08 (Diet 5), and 0.15 (Diet 6) g/kg MCE for eight weeks. Results showed that dietary MCE supplementation had no significant effect on the growth performance or muscle composition of crayfish. Conversely, supplementation with 0.02–0.04 g/kg MCE significantly increased the activities of superoxide dismutase (SOD), glutathione peroxidase (GPx), phenoloxidase (PO), and the total antioxidant capacity (T-AOC) in the hepatopancreas and plasma, while significantly reducing malondialdehyde (MDA) levels. Specifically, supplementation with 0.04 g/kg MCE significantly upregulated the hepatopancreatic mRNA expression levels of SOD, hemocyanin, GPx, and selenium-dependent glutathione peroxidase (Se-GPx). Furthermore, the challenge test demonstrated that supplementation with 0.04 g/kg MCE significantly improved crayfish survival under microcystin-LR (MC-LR) stress. Overall, supplementation with 0.04 g/kg MCE significantly improved the antioxidant capacity, immunity, and stress resistance of crayfish, suggesting its potential as an environmentally friendly immunostimulatory feed additive to protect against MC-LR stress in crayfish.

Mechanistic investigation of TRIB3-mediated growth, metastasis and ferroptosis in renal cell carcinoma - Wei Wang; Long Zhang; Tao Wu; Yuefeng Li; Haidong Wang; Haiqiao Huang; Yuexian Guo (Human Cell, 2026)

Tuning the glass transition temperature of two-photon polymerized elastomers for tailorable mechanical properties and enhanced recovery - Yu Long; Tao Wang; Yan Wang; Xiaolong Huang; Zhongyan Gong; Zhiyuan Ma; Yu Lei; Biwei Deng; Yan Li (Chemical Engineering Journal, 2026)

Dynamic atomic iodine anchoring switches oxygen reduction pathway to hydrogen peroxide on high-entropy sulfides for uranium extraction - Yifan Wang; Qiang Luo; Xuesen Li; Lei Sun; Qiang Su; Jiale Pu; Long Chen; Yongjie Yang; Tao Liu; Ning Wang (Chemical Engineering Journal, 2026)

Anaerobic Digestion of Sulfamethoxazole Pharmaceutical Wastewater Boosted by Conductive Materials: Focus on Efficiency and Microbial Synergies - Xi Long; Baowen Zhang; Chuanlin Cai; Wanying Li; Jialin Huang; Yanxiang Liang; Bin Kuang; Tao Wang (Water, Air, & Soil Pollution, 2026)

Molecular mapping of a novel non-canonical gibberellin-sensitive dwarfing gene Rht29 in wheat (Triticum aestivum) - Fuqiao Deng; Juanyu Zhang; Yanyan Tang; Furong Huang; Tao Li; Haili Zhang; Jinhui Wang; Junjun Liang; Guangbing Deng; Hai Long (Theoretical and Applied Genetics, 2026)

Exploring primate immune responses to SLA-I/II knockdown pig xenografts in humanized mice and rhesus monkeys - Ming-Hui Fang; Hao Feng; Kai Xu; Tang Hai; Song Chen; Ji-Long Ren; Wei-Gang Wang; Yuan-Tao Wang; Jun Zou; Fei Xu; Zi-Yue Wang; Yi-Wei Yao; et al. (Science China Life Sciences, 2026)

Stress Interference between Multi-radial Boreholes During Hydraulic Fracturing in Multilayered Reservoirs Based on the Discrete Lattice Method - Tengda Long; Xiaoguang Wu; Yazhou Shen; Zixiao Xie; Zhongwei Huang; Gensheng Li; Rui Yang; Zhaowei Sun; Tao Pan; Naikun Hu; Xiaohua Wang (Rock Mechanics and Rock Engineering, 2026)

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

Efficient degradation of polycarbonate via collaborative alcoholysis and hydrolysis - Li-Juan Liu; Si-Wei Wang; Yuan-Jun Fang; Kun-Long Yu; Xiong-Lei Wang; Tao Chang (Sustainable Chemistry and Pharmacy, 2026)

Orchestrated multicopper heterostructural motifs in MOF enable tandem CO2 valorization via photothermal-photocatalytic C–N coupling - Jian-Qiang Zhao; Hui-Li Zheng; Yu-Jia Cheng; Cheng-Xia Chen; Xiong-Feng Ma; Zheng Yin; Jia-Wei Li; Dong-Dong Ma; Hua Lin; Xin-Tao Wu; Cheng-Yong Su; Qi-Long Zhu (Science Bulletin, 2026)

Constructing core-shell BaTiO3@ZIF-67 derived composites for boosted piezocatalytic H2O2 production - Qiuchan Zhong; Yuyuan Liu; Guanghuan Li; Kexin Sun; Meien Chen; Yaoyao Tang; Bingyi Yan; Tao Long (Journal of Environmental Chemical Engineering, 2026)

An active cling film developed from pomelo peel for synergistic preservation of Oncorhynchus mykiss: Utilizing K/Fe enzyme-like materials and natural extracts - Tao Yu; Long Cheng; Yini Zhao; Long Gu; Hangfei Gao; Zicen Liu; Li Huang; Shuyan Bai; Dongli Qin; Peng Wang; Aimin Wang; Haijiao Xie; et al. (Food Packaging and Shelf Life, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

Moisture-driven ionogel neuromorphic sensor for apnea detection and event recognition in wearable patches - Xiu-juan Li; Fa Zhang; Ke-yan Li; Xin Li; Zhen-hui Tao; Ke-xin Wang; Zhen-yu Zhang; Guo Fang; Zi-xin Wang; Jia-yi Xie; Long Zhang; Chang-min Yu; et al. (Chemical Engineering Journal, 2026)

Resilience of Dehalococcoides enables complete reductive dechlorination of trichloroethene to ethene under high PFOS stress - Fang Zhang; Runlei Ge; Chongwen Shi; Tao Long; Kun Yang; Guanghe Li; Lifeng Cao (ENGINEERING Environment, 2026)

The specificity and selectivity of aptamer depends on the binding epitope: insights from aptamer Hislxl-2a - Xiaoli Liu; Xiangru Zhang; Xinhui Zhao; Mingyan Wu; Xinyue Li; Hengyi Lin; Mingxin Zhang; Zhenhao Long; Tao Bing (Analytica Chimica Acta, 2026)

TTM: A concise yet effective surface reconstruction approach for tunnel point cloud from mobile mapping system - Hao Cui; Jian Li; Qingwu Hu; Long He; Yiwen Tao; Lei Xu; Qingzhou Mao (Tunnelling and Underground Space Technology, 2026)

Physics-data driven approach for multi-objective intelligent prediction and optimization of deep soft rock tunnel stability - Yang Zhao; Yan-long Li; Lei She; Cheng-cheng Hu; Bin Li; Tao Wang; Xin-jian Sun; Xiao-jing Li (Transportation Geotechnics, 2026)

HGS+ enlarged vesicular compartments serve as the sites for coronavirus assembly at later infection stage - Xubing Long; Buyun Tian; Rongrong Chen; Rong Bai; Jinping Yang; Yushuang Fang; Xinyue Fu; Yanhong Xue; Wei Ji; Tao Xu; Zonghong Li (Science Bulletin, 2026)

Bioleaching of Co-bearing sulfide tailings by Acidithiobacillus ferrooxidans: Influencing factors, mechanism and kinetics - Qiya Bian; Sha Deng; Wei Yang; Tao Long; Sirui Chen; Chuntao Yan; Yuran Wang; Qubing Li (Minerals Engineering, 2026)

Plasma organophosphate ester exposure-associated microRNA expression profiles and their functional analysis in Chinese healthy adults - Xulin Zhang; Zirui Zhang; Yuxin Xu; Jiajia Zhu; Guang Chen; Rui Zeng; Wending Li; Xuedan Xu; Yu Yuan; Tao Jing; Tangchun Wu; Pinpin Long (Environmental Research, 2026)

Mechanistic insight into photodegradation of agricultural mulch films mediating the release micro(nano)plastic and dissolved organic matter to aquatic environments - Mengjie Wang; Huiming Yu; Jing Wei; Wenyi Xie; Xuwei Li; Lingya Kong; Ya Zhang; Tao Long; Qiong Wang; Shaopo Deng; Shixiang Gao; Wen-Tao Li (Chemical Engineering Journal, 2026)

From spent lithium-ion batteries to high-grade “urban mines”: A review of green recovery technologies for strategic metal resources of electrode material - Xiao-tian Zhao; Xiang-nan Zhu; Xin-long Li; Guang-liang Wei; Jing-tao Chen; Chun-liu Hu; Chun-chen Nie; Gu-yue Li; Yong-qiang Zhao (Chemical Engineering Journal, 2026)

Iatrogenic plasticizer Di(2-ethylhexyl) phthalate (DEHP) exposure increases Sepsis mortality risk: Machine learning implicates monocyte-driven immune dysregulation - Jun-jie Gao; Li-zhu Huang; Tao Wang; Yun-long Zhang; Kai Ye; Wei-hua Lu; Pu-hong Zhang (Toxicology and Applied Pharmacology, 2026)

Design, fabrication and multiple failure behavior of carbon fiber composite circumferential corrugated reinforced cylindrical shells under hydrostatic pressure - Yang-Xu Chong; Jin-Shui Yang; Da-Long Ding; Fang Yang; Hai-Dong Li; Yu-Yin Wei; Er Zhang; Jia-Dong Zeng; Guo-Tao Chen (Ocean Engineering, 2026)

DNA methylation mediates the association between organochlorine pesticides and MASLD: An epigenome-wide association study with integrated AOP framework - Yi Guo; Yutong You; Xin Guan; Yu Yin; Zhen Yin; Guorong Zhong; Chengyong Jia; Yuying Wen; Wenhui Li; Hui Zhao; Shengli Chen; Xi Wang; et al. (Journal of Hazardous Materials, 2026)

Elevation-driven divergence in soil colloid functionality governs polycyclic aromatic hydrocarbon mobility in the Three Gorges Reservoir riparian zone - Ying Xi; Jingzhong Long; Kun Li; Aoran Zhang; Biao Xiong; Tao Xu; David Johnson; Yuanfei Lv; Yingping Huang (Journal of Environmental Chemical Engineering, 2026)

Causal relationships between alzheimer’s disease genetics and brain connectivity alterations: a multi-modal mendelian randomization study with transcriptomic validation of 191 rs-fMRI and 635 DTI neuroimaging traits - Junjun Ji; Zhifan Li; Abao Xing; Gang Luo; Xiaobing Zhai; Wei Xu; Junrong Li; Tao Tan; Ruihong Jia; Yan Yan; Xianbin Zhang; Long Wang; et al. (Brain Imaging and Behavior, 2026)

Leaching mechanism and kinetics investigation of ilmenite leaching assisted by iron powder - Tao Long; Long Xiang; Rui Liu; Congxue Tian; Li Li; Jiesong Liu; Wenrong Xiang (Minerals Engineering, 2026)

Multi-compartment assessment of thallium in a typical agricultural watershed in China: Occurrence, criteria derivation, and risk characterization - Jinlin Jiang; Xuzhi Li; Yang Guo; Li Sun; Hao Zhang; Lei Wang; Tao Long (Journal of Hazardous Materials, 2026)

Integrated machine learning and density functional theory to design C₃N₅ piezo-catalysts toward precise control of selective reactive oxygen species and efficient water purification - Ting Li; Xianhu Long; Wei Liu; Fan Huang; Huinan Zhao; Tao Zhong; Jingyun Fang; Chun He (Journal of Hazardous Materials, 2026)

Molecular shifts in dissolved organic matter and microbial community assembly during vegetation restoration in karst ecosystems - Yuntian Long; Qian Tang; Wanglan Tao; Jianxing Li; Xiankun Li; Fuzhao Huang; Chuifan Zhou (Journal of Environmental Management, 2026)

Continuous biochar application results in higher greenhouse gas emissions than a single biochar application in an upland agroecosystem - Yan Zhang; Lihong Song; Kaiyu Li; Yi Liu; Tongmin Long; Tao Zhang; Zuyong Chen; Sanwei Yang (Journal of Environmental Sciences, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

The Impact of Delay Time on Blasting Mining Efficiency: Insights from Simulations and Field Experiments - Tao Hu; Xiang-long Li; Jian-guo Wang; Chun-ping Wu; Shu-feng Liang; Bao-qian Huan (Applied Geophysics, 2026)

The comprehensive comparison of syngas production systems driven by fossil energy and solar energy: Based on dry (CO2) reforming of methane - Ji-Long Yao; Bo-Yu Xu; Shi-Wei Wang; Zhen-Yu Zhang; Ting Li; Wei-Ting Li; Tao Xie (Fuel, 2026)

Spatial disparities and environmental justice in PM2.5 exposure among urban E-bike Commuters:A case study of Changsha - Xin Li; Tao Yang; Zhongwu Li; Zhiyong Long; Jie Liang; Ziqian Zhu; Jing Tong (Environmental Pollution, 2026)

Millennial-scale terrestrial weathering history and anthropogenic imprint in an alpine lake from Central Asia: evidence from the sedimentary geochemistry of Lake Sayram - Wen Liu; Yizhen Li; Long Ma; Jingyu Wang; Tao Zeng; Jilili Abuduwaili (CATENA, 2026)

Intelligent Control System for Particulate Matter: Real-Time Monitoring and Pollution Source Identification for Enhanced Efficiency - Peng Shi-Tao; Li Long-Chuang; Ye Yin; Hong Ning-ning; Zhang Jing; Chen Zi Jing; Du Hong-Bo (Water, Air, & Soil Pollution, 2026)

Dustfall source-apportionment and source-oriented health risk assessment using unsupervised machine learning, PMF, and HYSPLIT: Insights from a hotspot area in Xinjiang, China - Buweihaidiqie Maitituersun; Long Ma; Yizhen Li; Lingxin Kong; Tao Zeng; Wen Liu; Jilili Abuduwaili (Journal of Hazardous Materials, 2026)

Genetic and transcriptomic identification of WPG1 controlling nitrogen allocation-related leaf chlorisis and premature senescence in wheat - Haili Zhang; Li’ao Zhang; Qiang Li; Ling Yi; Juanyu Zhang; Yanyan Tang; Jinhui Wang; Junjun Liang; Tao Li; Fangyan Zhang; Yiran Cheng; Yi Wang; et al. (Theoretical and Applied Genetics, 2026)

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

Mutations in the clpS Gene of Riemerella anatipestifer Affect Stress Response and Bacterial Virulence - Liu Yufu; Liu Jiayi; Liao Ruixin; Rong Fang; Deng Yuanwen; Long Tao; Li Ladi; Cheng Xueyi; Li Sainan; Ouyang Zhengliang; Liu Wenhua; Chen Ruiai (Current Microbiology, 2026)

High temperature and high humidity (HTHH) alter flavor properties of Pu-erh tea associated with burnt aroma emergence - Tong Qin; Kaiyue Gao; Mengge Li; Yan Jin; Wenjie Sui; Min Zhang; Hairong Long; Tao Wu (Food Research International, 2025)

Grain yield and functional substance content in colored ratoon rice system under low solar radiation stress in southern China - Shaokun Song; Heng Zhang; Long Chen; Yixue Mu; Song Li; Ye Tao; Zaid Ulhassan; Haider Sultan; Lixiao Nie (Field Crops Research, 2025)

Developing water quality criteria and assessing ecological risks for 6PPD and 6PPD-Q in freshwater ecosystems - Hao Zhang; Li Li; Jinlin Jiang; Ziyan Zhou; Qiang Chen; Tao Long (Environmental Pollution, 2025)

Corrigendum to “Analytical method to evaluate aerodynamic damping of onshore wind turbine tower in operating state” [Eng Struct, vol. 343 (2025) /121001] - Tao Long; Yan Jiang; Guoqing Huang; Xuhong Zhou; Qingshan Yang; Rongfu Li (Engineering Structures, 2025)

Radial borehole fracturing in the multilayered shale oil reservoir based on a 3D discrete lattice model - Zixiao Xie; Tengda Long; Xiaoguang Wu; Zhongwei Huang; Gensheng Li; Xianzhi Song; Rui Yang; Tao Pan; Wenchao Zou; Zhaowei Sun; Yaoyao Sun; Naikun Hu; et al. (Engineering Geology, 2025)

Ultramicroporous MOF-enabled molecular confinement for efficient full-color and white-light emission - Jinling Huang; Haitao Li; Liping Wang; Qi-Long Zhu; Xin-Tao Wu; Yuehong Wen (Chemical Engineering Journal, 2025)

Synergistic effects and mechanism of recombinant viral vector-mediated STAT1 overexpression and STAT3 silencing on glioma U251 apoptosis - Xin-Long Hu; Hong Li; Guo-Dong Zhang; Chao Lin; Ping Huang; Xiu-Feng Chen; Fang Wan; Chang-Wu Dou; Hai-Tao Ju (Molecular Biology Reports, 2025)

Lithospermic acid targeting heat shock protein 90 attenuates LPS-induced inflammatory response via NF-кB signalling pathway in BV2 microglial cells - Jie Guo; Chen-guang Li; Feng-yi Mai; Jing-rong Liang; Ze-hao Chen; Jiao Luo; Ming-chao Zhou; Yu-long Wang; Wen-tao Yang (Immunologic Research, 2025)

Harnessing Plant Essential Oils to Combat Acinetobacter baumannii: Research Progress in Antimicrobial Mechanisms and Therapeutic Prospects - Shu-Yun Wei; Yu Sun; Qing Lu; Zhen Liang; Tao Zhu; Yu-Long Li; Ding-Hui Xu; Cai-Ying Li; Feng-Lan Feng; Hong Zeng (Current Microbiology, 2025)

Oxytocin-mediated neuroprotection in ischemic stroke: molecular mechanisms, therapeutic potential and clinical translational prospects - Yuan Chen; Tao Li; Long Zou; Yanhui Li (Metabolic Brain Disease, 2025)

Comprehensive Geophysical Characteristics and Exploration Significance of the Xiarihamu Super-Large Copper-Nickel Deposit in the East Kunlun Metallogenic Belt - Ji-en Dong; Bao-chun Li; Tao Wang; Yu-long Li; Xiao-jun Dong; Fu-chun Wang; Hai-kui Tong; Zhen-hua Zheng; Hua Li; Peng Wang (Applied Geophysics, 2025)

Chlorophyll a and photosynthetic carbon fixation in a tropical coral reef bay (Sanya Bay) of the northern South China Sea, with special reference to the effects of solar ultraviolet radiation B - Yukun Yao; Yingxin Li; Weihua Zhou; Aimin Long; Xiangcheng Yuan; Tao Li; Sheng Liu; Hui Huang (Marine Pollution Bulletin, 2025)

Microbial community dynamics and ecological interactions during an atypical winter Cerataulina pelagica (Bacillariophyta) bloom in Laizhou Bay, southern Bohai Sea - Long Yang; Hongwei Wang; Zhengguo Cui; Hualong Wang; Xiaokun Ding; Di Zhang; Huanyu Zhang; Sheng Li; Tao Jiang (Marine Environmental Research, 2025)

Analytical method to evaluate aerodynamic damping of onshore wind turbine tower in operating state - Tao Long; Yan Jiang; Guoqing Huang; Xuhong Zhou; Qingshan Yang; Rongfu Li (Engineering Structures, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

An innovative and clean strategy to recover copper resources from waste printed circuit boards: Malic acid leaching and micro-nano copper preparation - Xi-guang Li; Xin-long Li; Guang-liang Wei; Jing-tao Chen; Xiao-tian Zhao; Chun-chen Nie; Lin Li; Shuai Yan; Xiang-nan Zhu (Chemical Engineering Journal, 2025)

Smart weeding system with multi-sensor fusion for tomato plant detection and targeted micro-spraying of intra-row weeds - Jia-Le Li; Wen-Hao Su; Rui Hu; Long-Tao Niu; Qi Wang (Computers and Electronics in Agriculture, 2025)

Albumin mediates the association between maternal exposure to multiple metals and gestational diabetes mellitus: Findings from the Guangxi Birth Cohort Study - Hualong Qiu; Yu Bao; Shengzhu Huang; Yuen Zhong; Caitong He; Long Tian; Yu Zhang; Bangzhu Luo; Tao Liang; Baohong Pang; Mujun Li; Hong Cheng; et al. (Journal of Trace Elements in Medicine and Biology, 2025)

Sb-doped Cu-Fe/TiO2 catalysts with enhanced K-poisoning resistance for simultaneous NO and CO removal - Yang-wen Wu; Zheng-long Wu; Hai-yuan Zhao; Han-wen Wang; Yao Dong; Xin-yue Zhou; Jing-tao Li; Qiang Lu (Journal of Environmental Chemical Engineering, 2025)

Calcium and molybdenum isotopes trace eclogitic crust recycling in formation of unique carbonatite-hosted Mo-REE-U-Nb deposits in orogenic belt - Li Tang; Tao Zeng; Thomas Wagner; Tobias Fusswinkel; Long-Long Chen; Jie Li; Rui Wang (Earth and Planetary Science Letters, 2025)

Nitrogen-oxygen radical generator-mediated in situ activation of live-cell prodrug for rational combination therapy - Ting Hou; Zi-Tao Shen; Wan-Ting Chen; Yang Song; Yin-Yu Yan; Zi-Jiang Luo; You-Yang Li; Yu-Ting Shan; Rui-Cheng Li; Tian-Yu Shen; Jia-Qin Long; Li Yin; et al. (Chemical Engineering Journal, 2025)

OsATG1 and OsATG8 exhibit autophagy-independent functions to oppositely regulate ROP GTPase-mediated plant immunity in rice - Feng He; Hui Tao; Ruyi Wang; Jinling Liu; Zeyun Hao; Debao Wang; Xuetao Shi; Fan Zhang; Jiawei Long; Hao Zhang; Xiao Yang; Mengchao Qin; et al. (Molecular Plant, 2025)

Indirect competitive advantages of invasive over native plants under multiple stressors - Xiong Shi; Wei-Tao Li; Mark van Kleunen; Long Li; Yu-Long Zheng (Journal of Environmental Management, 2025)

The effects of temperature on the nutritional quality of crayfish (Procambarus clarkii) were analyzed by combining transcriptome, metabolome and intestinal microbiota - Ruichun Li; Wenqi Qian; Li Huang; Shuyan Bai; Chenhui Li; Ningning Du; Long Cheng; Lei Xiu; Linhai Yu; Tao Guan; Jian Li; Shilong Chen; et al. (Food Bioscience, 2025)

Chitosan/PEO@Eu-MOF nanofiber membrane-based test strip for visual detection of tetracycline with smartphone-assisted analysis - Wei Pan; Zi-Han Zhu; Yan-Shen Zhao; Jie-Liu; Zhi-Guang Zhang; Gui-Xia Li; Tao Yu; Zhong-Zhi Han; Yun-Ze Long; Gui-Feng Yu (Chemical Engineering Journal, 2025)

Exploring the role of physical factors in microplastic migration and retention within porous media: Mechanistic insights through microfluidic visualization - Junjie Wang; Yanyan Gao; Lingling Ren; Hailong Zhao; Tao Long; Yan Li; Christos Tsakiroglou; Omar Alfarisi; Xiaopu Wang (Chemical Engineering Journal, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

High value-added conversion of atmospheric pollutants and greenhouse gases: assessment of bottlenecks and optimization strategies for mainstream catalytic technology - Tao Zhong; Xianhu Long; Zhangnan Yao; Ting Li; Huinan Zhao; Su Tang; Shuanghong Tian; Chun He (Journal of Cleaner Production, 2025)

Hypoxia-preconditioned ADSC exosomes encapsulated in a multifunctional dual-network hydrogel promote the healing and functional regeneration of seawater-immersed wounds - Jie Li; Zishuo Wang; Wenjing Yang; Yongchao Zhou; Tao Fu; Yuhui Zhang; Xuzhou Duan; Dong Liu; Lingtong Kong; Yan Shang; Yuchen Zhang; Xuhui Wang; et al. (Chemical Engineering Journal, 2025)

A specific energy and penetration interaction-based method for optimizing TBM operational parameters in hard rock - Lei She; Cheng-cheng Hu; Yan-long Li; Dong-feng Li; Zhao-Yu Li; Tao Fang; Ji-guang Zheng (Tunnelling and Underground Space Technology, 2025)

Development of dynamic topology optimization method for offshore jacket platforms - Yu-Tao Guo; Kang Ge; Chen Wang; Xiao-Long Zhao; Bin-Bin Li (Ocean Engineering, 2025)

A combined DFT and experimental study for the synergistic removal of NO and toluene on FeVO4/TiO2 catalysts: Insights from redox ability and charge transfer - Yang-Wen Wu; Zheng-Long Wu; Yi-Fei Yu; Xu Su; Xin-Yue Zhou; Bing Zhang; Li Zhao; Jing-Tao Li; Qiang Lu (Process Safety and Environmental Protection, 2025)

Zircon and apatite constraints on the key factors controlling porphyry Mo mineralization in the Shijiawan deposit: Implication for Mo metallogeny in the Qinling Orogenic Belt - Long-Long Chen; Li Tang; Peng-Rui Lv; Ya-Peng Chen; Tao Zeng (Lithos, 2025)

Alternating electric field as an effective inhibitor of bioavailability and phytotoxicity of heavy metals during electric field-assisted aerobic composting - Tao Fu; Chang Shen; Huan Mi; Jiahuan Tang; Long Li; Hao Lin; Huayuan Shangguan; Zhen Yu (Journal of Hazardous Materials, 2025)

Organic acid-enhanced production of hydroxyl radicals during H2O2-based chemical oxidation for the remediation of contaminated soil - Guangxia Liu; Mei Li; Jing Hua; Jing Wei; Yan Zhou; Shaopo Deng; Tao Long; Ning Chen; Guodong Fang; Shengtian Zhang (Journal of Hazardous Materials, 2025)

Shifts in soil prokaryotic community structure due to clear-cutting secondary Acacia mangium forests and replacing with Eucalyptus urophylla - Yun-Long Zhang; Ning Pan; Wen-Tao Qiao; Richard P. Dick; Dao-Lin Du; Kun Chen; Shan-Shan Qi; Yan Li; Yi Zhou; Yong-Feng Wang (Journal of Environmental Management, 2025)

Visible light can also efficiently activate chlorine dioxide for the abatement of micropollutants - Bin Zhang; Zhiyun Long; Ge Zeng; Wenjun Zhang; Peng Su; Xiangyang Hou; Qixiao Lv; Wenqi Li; Jin Jiang; Zihao Wu; Tao Yang (Chemical Engineering Journal, 2025)

Genetic identification and characterization of quantitative trait loci for wheat grain size-related traits independent of grain number per spike - Tao Li; Yanyan Tang; ZhengXi Lin; Jinghui Wang; Juanyu Zhang; Qiang Li; Furong Huang; Junjun Liang; Haili Zhang; Zehou Liu; Jun Li; Wuyun Yang; et al. (Theoretical and Applied Genetics, 2025)

State-of-the-art review on liberation of cathode material in pretreatment recycling of spent lithium-ion battery - Chenye Wang; Ren Tao; Peng Xing; Jun Ni; Zhigen Cun; Shaojun Liu; Xingrui Wang; Yu Dai; Zhibin Long; Zhenhua Sun; Huiquan Li (Resources, Conservation and Recycling, 2025)

Mussel settlement mediated by calcined mussel shell powder through outer membrane protein gene ompW - Yuyi Wang; Yu Tao; Ruiheng Chang; Zheng Li; Lihua Peng; Jin-Long Yang; Xiao Liang (International Biodeterioration & Biodegradation, 2025)

Exogenous Application of Silicon and Spermidine Alleviate Cadmium Toxicity by Modulating Endogenous Polyamines Level and Glutathione Metabolism in Salix matsudana Koidz. Seedlings - Weili Mao; Long Guo; Tao Sun; Xiaoxuan Song; Shanshan Gao; Xue Li; Kaiyuan Yu; Yanan Ruan (Journal of Plant Growth Regulation, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Offshore wind turbine monopiles under real wind and wave conditions: Considering cyclic softening of clays - Ling-Yu Xu; Jin-Tao Huang; Lei Liu; Cheng-Xiang Song; Zheng-Long Zhou; Zhao-Yan Li; Fei Cai; Guo-Xing Chen (Ocean Engineering, 2025)

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Pore-scale visualization of LNAPL displacement by chemical agents in heterogeneous groundwater system - Yan Li; Tao Long; Hangyu Li; Xiaopu Wang (Science of The Total Environment, 2025)

Fecal microbiota transplantation: transitioning from chaos and controversial realm to scientific precision era - Xinjun Wang; Di Zhao; Dexi Bi; Long Li; Hongliang Tian; Fang Yin; Tao Zuo; Gianluca Ianiro; Ning Li; Qiyi Chen; Huanlong Qin (Science Bulletin, 2025)

Mechanism of synergistic effect of aluminum ions and water glass on talc flotation depression - Tao Long; Qubing Li; Wei Yang; Sha Deng; Xiangyu Peng; Jianping Jin (Minerals Engineering, 2025)

Description of three new species of Trigonidiidae Saussure, 1874 from China (Orthoptera: Grylloidea) - Tao Li-Long; Yang Rui-Ying; He Zhi-Xin; Ma Li-Bin (Journal of Asia-Pacific Entomology, 2025)

Ultrasound-assisted extraction of flavonoids from Rudbeckia hirta L. flowers using deep eutectic solvents: Optimization, HPLC analysis and anti-inflammatory activity - Jiang-Rui Wang; Yin-Long Li; Hai-Tao Zhang; Zhao-Bao Xiang; Jing Zuo; Bo Peng; Xing-Yu Liu; Hong Ou (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Optimizing sowing date to enhance grain yield and quality formation of colored rice in tropical regions of China - Shaokun Song; Rui Yue; Long Chen; Song Li; Ye Tao; Zhenxiang Zhou; Lixiao Nie (Field Crops Research, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Unveiling Latent interaction mechanisms influencing the spatial pattern of soil salinity in arid Oases: Insights from integrated modeling - Tao Zeng; Yizhen Li; Long Ma; Lingxin Kong; Jingjing Zhang; Jilili Abuduwaili (CATENA, 2025)

Green revolution gene drives adaptation of Arabidopsis to the extremely high altitude - Xing-Hui Hou; Yong-Chao Xu; Tianshu Sun; Yan-Bo Gong; Xin-Tong Li; Guang-Teng Jin; Yu-Tao Bian; Yi-Ni Liu; Juan Jiang; Xiao-Min Niu; Hongya Gu; Ya-Long Guo (Science China Life Sciences, 2025)

Response of soil organic carbon stocks and soil microbial biomass carbon to natural grassland conversion: A global meta-analysis - Yijun Cai; Yuwen Yang; Jinlin Jiang; Tao Long; Xueyuan Gu; Yang Guo; Ming Li; Yufeng Xie (Science of The Total Environment, 2025)

Phosphorus speciation in the hyporheic zone and its response to sediment-water quality-biological activity coupling effect - Yue Qu; Jinxi Song; Yongqing Long; Nan Li; Songzhe Fu; Bin Tang; Qihao Tao; Qifan Cui; Ken Qin (Journal of Environmental Management, 2025)

Unintentional emissions of polychlorinated naphthalenes in China: Sources, composition, and historical trends - Ye Huang; Lin Huang; Ying Li; Nazupar Sidikjan; Yunshan Zhang; Yan Chen; Yangmin Chen; Ye Li; Wei Du; Long Chen; Yan Wu; Shanshan Zhang; et al. (Journal of Environmental Sciences, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Insomnia in Parkinson’s Disease: Causes, Consequences, and Therapeutic Approaches - Xiaoyu Duan; Hanshu Liu; Xinyu Hu; Qinwei Yu; Guiying Kuang; Long Liu; Shurui Zhang; Xinyi Wang; Jingwen Li; Danfang Yu; Jinsha Huang; Tao Wang; et al. (Molecular Neurobiology, 2025)

Design, synthesis and herbicidal activity of novel cyclohexanedione derivations containing pyrazole and pyridine groups as potential HPPD inhibitors - Shuai-Tao Hou; Ling Han; Wen-Rui Li; Guang-Yu Dai; Yu Liu; Ai-Min Lu; Chun-Long Yang; Min Chen (Molecular Diversity, 2025)

The independent and combined associations of nocturnal sleep duration, sleep midpoint, and sleep onset latency with global cognitive function in older Chinese adults - Xueyao Wu; Jiaqiang Liao; Xin Chen; Jinyu Xiao; Xinyang Dui; Tianpei Ma; Lin Hu; Xunying Zhao; Qian Bu; Mengyu Fan; Tao Zhang; Lu Long; et al. (GeroScience, 2025)

Comparative analysis of carotenoids, fatty acids, minerals, tastes, and odor in the skin of wild versus farmed large yellow croaker: Superior nutritional benefits with elevated heavy metal risks - Jia-Lang Zheng; Tao Zhu; Wang-Yang Jin; Qing-Hao Zhan; Fa-Guo Wan; Yong-Long Chen; Tian-Hong Chen; Shun Chen; Qing-Ling Zhu; Shuang Chen; Wei-Ye Li; Yi-Fan Liu; et al. (Aquaculture, 2025)

The miR172a–SNB module orchestrates both induced and adult-plant resistance to multiple diseases via MYB30-mediated lignin accumulation in rice - He Wang; Zhe-Xu Wang; Hong-Yuan Tian; Yu-Long Zeng; Hao Xue; Wan-Ting Mao; Lu-Yue Zhang; Jun-Ni Chen; Xiang Lu; Yong Zhu; Guo-Bang Li; Zhi-Xue Zhao; et al. (Molecular Plant, 2025)

Multi-man–robot collaborative disassembly line balancing optimization via mixed-integer programming and genetic Jaya algorithm - Tao Yin; Jiapeng Wu; Jungang Cao; Yunwei Huang; Chuan Li; Jianyu Long (Journal of Cleaner Production, 2025)

Spectral properties regulation for the performance improvement of solar-driven methane dry reforming reactor based on the photothermal synergistic catalysis - Ji-Long Yao; Zhen-Yu Zhang; Bo-Yu Xu; Ting Li; Tao Xie (Fuel, 2025)

Study on organic carbon in medium-low mature shale oil reservoirs rich in type II kerogen: Oxidation behavior, thermal effect, and kinetics - Wanfen Pu; Xing Jin; Yuanyuan Bai; Shuai Zhao; Long He; Yibo Li; Tao Li (Fuel, 2025)

Enrichment of antioxidant peptide from rice protein hydrolysates via rice husk derived biochar - Hui-Zhen Tao; Wen-Bin He; Li Ding; Li Wen; Zhou Xu; Yun-Hui Cheng; Mao-Long Chen (Food Chemistry, 2025)

Dietary Probiotic Rhodopseudomonas palustris Formulation Improves Growth Performance, Muscle Composition, Digestive Enzyme Activity, Non-Specific Immunity and Disease Resistance of Juvenile Ivory Shell (Babylonia areolata) - Xiao Wang; Yao-Peng Lu; Ze-Long Zhang; Pei-Hua Zheng; Jun-Tao Li; Xiu-Xia Zhang; Jia-Jun Li; Heng-Mei Wu; Jian-An Xian (Fishes, 2024)
Rhodopseudomonas palustris (RP) are known anaerobic bacteria with probiotic properties containing several bioactive compounds and enzymes that benefit aquatic animals. However, studies on the use of RP on aquatic animal species are limited. This study investigated the effects of dietary supplementation with RP formulation on the growth, non-specific immunity, and disease resistance of juvenile ivory shells (Babylonia areolata). The experiment was conducted for 8 weeks, with B. areolata fed a control diet (RP0) and four diets containing four different RP formulations, with doses of 1 (RP1), 5 (RP2), 10 (RP3), and 20 (RP4) g/kg, respectively. Higher levels of R. palustris in the formulation led to increased final weight, weight gain, and specific growth rate in B. areolata. The crude protein content was significantly higher in the RP4 group compared to the RP0 group. However, there was no significant difference in the crude lipid content. Higher levels of R. palustris in the RP4 formulation group increased the trypsin and lipase activities. Dietary supplementation with RP significantly increased the total antioxidant capacity, superoxide dismutase, and catalase activities and decreased the malondialdehyde content in B. areolata. Acid phosphatase and alkaline phosphatase activities were significantly increased in the RP4 group compared to the RP0 group. Dietary RP significantly increased the expression levels of antioxidant-related (superoxide dismutase, Cu/Zn-superoxide dismutase, glutathione S-transferase A-like, ferritin) and immune-related (acid phosphatase, cytochrome c) genes. Higher levels of R. palustris in the formulations RP3 and RP4 increased the survival rate of B. areolata challenged with Vibrio parahaemolyticus. These findings indicate that R. palustris preparation could improve growth performance, muscle composition, and digestive capacity and may act as an immune booster for preventing disease in B. areolata.

Formation and evolution of thermokarst landslides in the Qinghai-Tibet Plateau, China - Tao Wei; Hao Wang; Peng Cui; Yan Wang; Bo Zhang; Rui-Long Wei; Zhen-Xing Liu; Chao-Yue Li (Science of The Total Environment, 2024)

Novel catalyst-free activation of chlorine by visible light for micropollutant abatement - Ge Zeng; Linqian An; Maoju Jiang; Wenqi Li; Xiangyang Hou; Peng Su; Minchao Liu; Haijun Cheng; Zhiyun Long; Jingxin Yang; Jun Ma; Tao Yang (Journal of Hazardous Materials, 2024)

Seasonality shapes the microbiota and metabolome of strong-flavor Baijiu during fermentation and affects its flavor characteristics - Li-Juan Chai; Jing-Yi Zhang; Tao Gao; Long-Yun Zhang; Xiao-Juan Zhang; Zhen-Ming Lu; Jin-Song Shi; Xiang Chen; Zheng-Hong Xu (Food Bioscience, 2024)

Development of multifunctional fruit packaging by incorporating starch aldehyde-quercetin conjugate into chitosan coating films - Yufeng Sun; Yang Ju; Lili Wang; Ran Tao; Long Li; Bei Fan; Fengzhong Wang (Food Hydrocolloids, 2024)

Fine mapping and candidate gene mining of QSc/Sl.cib-7H for spike compactness and length and its pleiotropic effects on yield-related traits in barley (Hordeum vulgare L.) - Jinhui Wang; Yanyan Tang; Jin Li; Juanyu Zhang; Furong Huang; Qiang Li; Baowei Chen; Li’ao Zhang; Tao Li; Haili Zhang; Junjun Liang; Guangbing Deng; et al. (Theoretical and Applied Genetics, 2024)

MEIKIN expression and its C-terminal phosphorylation by PLK1 is closely related the metaphase–anaphase transition by affecting cyclin B1 and Securin stabilization in meiotic oocyte - Li-Hua Fan; Shu-Tao Qi; Zhen-Bo Wang; Ying-Chun Ouyang; Wen-Long Lei; Yue Wang; Ang Li; Feng Wang; Jian Li; Li Li; Yuan-Yuan Li; Yi Hou; et al. (Histochemistry and Cell Biology, 2024)

Concentric Compressive Behavior and Design of Stainless Steel–Concrete Double-Skin Composite Tubes Influenced by Dual Hydraulic Pressures - Jian-Tao Wang; Yang Yang; Kai-Lin Yang; Deng-Long Hu; Long-Bo Xu; Jun-Xin Li (Journal of Marine Science and Engineering, 2024)
The external hydraulic pressure and internal medium pressure acting on submarine pipelines can lead to the coupling effect of active and passive constraints on the mechanical performance of steel–concrete double-skin composite tubes, resulting in a significantly different bearing capacity mechanism compared to terrestrial engineering. In this paper, the full-range concentric compressive mechanism of new-type stainless steel–concrete double-skin (SSCDS) composite tubes subjected to dual hydraulic pressure was analyzed by the finite element method. The influence of geometric–physical parameters at various water depths was discussed. The key results reveal that imposing dual hydraulic pressures significantly improves the confinement of double-skin tubes to encased concrete, resulting in a higher axial compressive strength and a non-uniform stress distribution; increasing the material strengths of concrete, outer tubes and inner tubes results in an approximately linear enhancement in axial bearing capacity; enhancing the diameter-to-thickness ratios of outer tubes and inner tubes can decrease the bearing capacity of SSCDS composite tubes; and the axial compression strength of SSCDS composite tubes with a higher hollow ratio of 0.849 tends to decrease with increasing outer hydraulic pressure. A practical method that integrates the effects of dual hydraulic pressures was developed and validated for the strength calculation of SSCDS composite tubes. This research provides fundamental guidelines for the application of pipe-in-pipe structures in deep-sea engineering.

Dynamics of phytoplankton assemblages determined by the HPLC–PIGMENTUM approach and the related environmental variables in the northern Chinese sea - Long Yang; Zhengguo Cui; Jian Zhang; Hongwei Wang; Hanbai Wang; Di Zhang; Xiaokun Ding; Daojun Zha; Li Gao; Tao Jiang (Marine Pollution Bulletin, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Flavopiridol inhibits oocyte maturation, reduces oocyte quality and blocks cumulus cell function - Xiao-Zhen Li; Li-Tao Yi; Qing-Yuan Sun; Chang-Long Xu; Shen Yin (Toxicology Letters, 2024)

Dual-continuous microneedle patch integrating transdermal delivery of pH-sensitive licorzinc MOFs and Zn2+ hydrogel sensors for treating alopecia areata - Hang Ruan; Yuwen Zhong; Huining Ding; Zehui He; Jiaqi Li; Meng Long; Zhi Wang; Qing Xia; Teng Guo; Chunyun Zhu; Tao Yang; Nianping Feng; et al. (Chemical Engineering Journal, 2024)

Greater variation of soil organic carbon in limestone- than shale-based soil along soil depth in a subtropical coniferous forest within a karst faulted basin of China - Tao Yang; Genzhu Wang; Jie Long; Jinyan Mi; Aijia Yu; Xingyu Liu; Haoran Zhang; Liang Dong; Zihao Li; Chenghao Zheng; Saman Herath; Jinxing Zhou; et al. (CATENA, 2024)

Comparative study on the quality of wild and ecologically farmed large yellow croaker through on-site synchronous sampling from the Nanji Archipelago in the East China Sea - Jia-Lang Zheng; Yong-Long Chen; Fa-Guo Wan; Qing-Hao Zhan; Tian-Hong Chen; Shun Chen; Qing-Ling Zhu; Li-Hua Jiang; Wei-Ye Li; Wen-Tao Ye; Yi-Fan Liu; Wei-Hua Song; et al. (Aquaculture, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Curcumin loaded high internal phase emulsions: Formulation and potential to alleviate DSS-induced ulcerative colitis - Xiao-Long Li; Bao-Qiu Yang; Wen-Jie Liu; Han Tao; Bao Zhang (Food Bioscience, 2024)

Sustainably sourced and DOPO-derived triols as hardeners for epoxy thermosets: A promising solution to synchronously improve flame retardancy, mechanical strength and toughness - Ze-Tao Xiao; Guan-Long Wu; Tian-Mo Yang; Yu Li; Yuan Hu; Manfred Döring; Xin Wang (Chemical Engineering Journal, 2024)

Body temperature-triggered adhesive ionic conductive hydrogels for bioelectrical signal monitoring - Xuelan Li; Yue Sun; Shenglong Wang; Guo Tian; Tao Yang; Longchao Huang; Yong Ao; Boling Lan; Jieling Zhang; Tianpei Xu; Yang Liu; Long Jin; et al. (Chemical Engineering Journal, 2024)

Treatment advances of hazardous solid wastes from oil and gas drilling and production processes - Xiaopu Wang; Wenlong Jin; Yan Li; Shuyang Liu; Jianchun Xu; Junrong Liu; Hangyu Li; Tao Long (Chemical Engineering Journal, 2024)

Molecular insights into the catalytic mechanism of a phthalate ester hydrolase - Ning Wang; Nan Zhang; Mei-Ling Sun; Yan Sun; Qing-Yu Dong; Yu Wang; Zeng-Tian Gu; Hai-Tao Ding; Qi-Long Qin; Yong Jiang; Xiu-Lan Chen; Yu-Zhong Zhang; et al. (Journal of Hazardous Materials, 2024)

Insight into the influence mechanism of chloride ions towards in-situ electric-induced uranium incorporation into magnetite - Mi Li; Xin Ma; Xiao-yan Wu; Yi-long Hua; Xiao-wen Zhang; Qi Fang; Tao Cai (Journal of Cleaner Production, 2024)

Efficient removal of perrhenate/pertechnetate by a pyridinium-based porous polymer - Miaomiao He; Yuxuan Chen; Guangyuan Chen; Wenhao Li; Mingxing Zhang; Chao Zhang; Hao Zhang; Xingyi Long; Kui Tang; Tao Duan; Lin Zhu (Environmental Pollution, 2024)

Organofluorinated Ag/2D diamond nanocomposites achieve simultaneously ultra-low friction and wear in self-lubricating epoxy - Qingzhao Cai; Chengcheng Jiao; Junhao Wu; Shanqin Ge; Wei Li; Long Chen; Genxiang Gong; Jiamin Yu; Yaokang lv; Jinhong Yu; Kazuhito Nishimura; Nan Jiang; et al. (Chemical Engineering Journal, 2024)

Rational design of robust Cu@Ag core-shell nanowires for wearable electronics applications - Yu-Chieh Kuo; Jiajun Fan; Lingqing Zong; Fandi Chen; Ziheng Feng; Chao Liu; Tao Wan; Zi Gu; Long Hu; Peiyuan Guan; Chun-Ho Lin; Mengyao Li; et al. (Chemical Engineering Journal, 2024)

Bimetallic porphyrin PET radiotracers for Low-Dose MRI contrast enhancement - Chen Xie; Xiong Li; Leilei Zhang; Ho-Fai Chau; Waygen Thor; Wing Sze Tam; Benjamin Woolley; Mingjun Jiang; Chi-Fai Ng; Mauro Botta; Tao Zhang; Nicholas J. Long; et al. (Chemical Engineering Journal, 2024)

Treating waste with waste: adsorption behavior and mechanism of phosphate in water by modified phosphogypsum biochar - Li-li Shan; Ruo-shan Wang; Hai-tao Lai; Ze-bing Zhu; Yu Chen; Zhu-ye Ni; Chang-long Pang; Qiu-zhuo Zhang (Environmental Science and Pollution Research, 2024)

Data driven damping separation method for the Mega-offshore wind turbine tower - Gang Liu; Jun Luo; Guoqing Huang; Rongfu Li; Weidong Ji; Tao Long (Ocean Engineering, 2024)

First identification of Mid-Miocene north–south trending dikes in the eastern Qiangtang terrane, eastern Tibet: Mantle melting and implications for plateau uplift - Chuan-Bing Xu; Jun Wang; Qiang Wang; Andrew C. Kerr; Wu-Fu Li; Jin-Heng Liu; Bing-Zhang Wang; Shan-Ping Li; Chun-Tao Wang; Zi-Long Wang; Lin Gong (Lithos, 2024)

Optimal emission control plan aiming to basically eliminate PM2.5 heavy pollution in North and Northwest China in 2018 - Zhilan Ye; Long Cheng; Jie Li; Fei Pan; Wenyi Yang; Xueshun Chen; Huiyun Du; Tao Wang; Zhe Wang; Zifa Wang (Journal of Cleaner Production, 2024)

Recycled lower oceanic crust signal in early Jurassic A1-type granites, South China: Implications for flat-slab subduction and mantle heterogeneity in the continental back-arc region - Bo Yan; Wu-Xian Li; Xiao-Long Huang; Ji-Hua Tao (Chemical Geology, 2024)

A sustainable method to increase the strength of warm permafrost: Ice nucleation active bacteria-based - Juanjuan Zheng; Liyun Tang; Peiyong Qiu; Jianguo Zheng; Li Han; Gaosen Zhang; Long Jin; Tao Zhao; Yongtang Yu; Hailiang Jia (Cold Regions Science and Technology, 2024)

Experimental evidence that nitrogen-fixing cyanobacterium Trichodesmium spp. supplies new nitrogen source to marine phytoplankton - Shuang-Qing Li; Yan Xiao; Hai-Long Huang; Zhen Luo; Tao-Ran Sun; Hua-Yang Gao; Xin-Wei Wang; Hai-Bo Jiang (Frontiers in Marine Science, 2024)
In oligotrophic oceans, primary productivity is widely limited by nitrogen bioavailability. The broadly distributed and abundant nitrogen-fixing cyanobacterium Trichodesmium plays an important role in the oceanic nitrogen and carbon cycles by providing a “new” source of nitrogen to many non-diazotrophic microbes, thereby driving new primary production in the ocean. However, the underlying process and mechanism of nitrogen supply from Trichodesmium to other phytoplankton remain unclear. Here, our results demonstrated that the fixed nitrogen released by Trichodesmium could sustain the growth of a non-nitrogen-fixing cyanobacterium Synechococcus sp. PCC 7002, including a mutant strain (Mut- ureA ) that cannot use urea. However, the growth rate of Mut- ureA was approximately 20% lower than that of the wild strain when Trichodesmium filtrate was used for nitrogen supply. This result was consistent with the composition of the Trichodesmium exudate, in which urea comprised more than 20% of the total fixed nitrogen that was released. It is evident from the experiments that a fraction of the Trichodesmium -derived nitrogen was not available to Mut- ureA . Our results suggested that Trichodesmium produces dissolved organic nitrogen, especially a certain amount of urea as a “new” nitrogen source, benefiting in particular populations of surrounding phytoplankton species.

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Time-frequency analysis of nonlinear structures under nonstationary excitation by directly solving structural dynamic equation through absolute displacement - Xi-Mei Li; Ting-Long Zhao; Cheng Tao (Soil Dynamics and Earthquake Engineering, 2024)

Macaque Brainnetome Atlas: A multifaceted brain map with parcellation, connection, and histology - Yuheng Lu; Yue Cui; Long Cao; Zhenwei Dong; Luqi Cheng; Wen Wu; Changshuo Wang; Xinyi Liu; Youtong Liu; Baogui Zhang; Deying Li; Bokai Zhao; et al. (Science Bulletin, 2024)

Cancer risk associated with low-dose ionizing radiation: A systematic review of epidemiological and biological evidence - Shu Min Tao; Le Le Wang; Min Da Li; Jing Wang; Hong Mei Gu; Long Jiang Zhang (Mutation Research - Reviews in Mutation Research, 2024)

Eocene rhyolites in the Shanglaxiu-Xialaxiu area of north-eastern Qiangtang Block, Tibet: Partial melting of juvenile crust? - Yi-Wen Wei; Jun Wang; Qiang Wang; Bing-Zhang Wang; Andrew C. Kerr; Wu-Fu Li; Shan-Ping Li; Jin-Heng Liu; Chun-Tao Wang; Zi-Long Wang (Lithos, 2024)

Combining genome-wide association study and linkage mapping in the genetic dissection of amylose content in maize (Zea mays L.) - Wei Dai; Qinglin Li; Tao Liu; Ping Long; Yao He; Mengxiang Sang; Chaoying Zou; Zhong Chen; Guangsheng Yuan; Langlang Ma; Guangtang Pan; Yaou Shen (Theoretical and Applied Genetics, 2024)

Empagliflozin rescues lifespan and liver senescence in naturally aged mice - Jiangchuan Long; Ziyu Ren; Yaqian Duan; Wei Tao; Xi Li; Shengbing Li; Ke Li; Qixuan Huang; Jie Chen; Mengliu Yang; Yang Li; Xie Luo; et al. (GeroScience, 2024)

Lacustrine shale lithofacies and depositional environment in the paleocene second member of the funing formation, subei basin, China: Insights into shale oil development prospects - Xiaojie Fan; Yangbo Lu; Zhanhong Liu; Yongchao Lu; Jingyu Zhang; Kong Deng; Tao Zhou; Hao Tai; Long Li (Marine and Petroleum Geology, 2024)

A functional study reveals CsNAC086 regulated the biosynthesis of flavonols in Camellia sinensis - Sa-Sa Song; Wei-Xi Ran; Long-Han Gao; Yu-Chun Wang; Wu-Yun Lv; Yu Tao; Liang Chen; Chun-Fang Li (Planta, 2024)

A newly isolated strain of Bacillus subtilis W2Z exhibited probiotic effects on juvenile red claw crayfish, Cherax quadricarinatus - Ze-Long Zhang; Jia-Jun Li; Si-Wen Xing; Yao-Peng Lu; Pei-Hua Zheng; Jun-Tao Li; Chen-Guang Hao; Jia-Rui Xu; Jian-An Xian; Li-Min Zhang; Xiu-Xia Zhang (Aquaculture, 2024)

Integration of transcriptome, gut microbiota, and physiology reveals toxic responses of the red claw crayfish (Cherax quadricarinatus) to imidacloprid - Yao-Peng Lu; Jia-Han Liu; Xiu-Xia Zhang; Chi Xu; Pei-Hua Zheng; Jun-Tao Li; Jia-Jun Li; Dong-Mei Wang; Jian-An Xian; Ze-Long Zhang (Journal of Hazardous Materials, 2024)

Micro-structure change and crystal-structure modulated of oxygen carriers for chemical looping: Controlling local chemical environment of lattice oxygen - Da Song; Tao Long; Cuiqin Li; Yang Li; Mingyang Fan; Yonghao Lu; Yuchao Zhou; Haitao Chen; Yan Lin; Zhen Huang; Fang He (Fuel, 2024)

Emergence of blaNDM-5–bearing IncHI2/ST2 and p0111 multidrug-resistance plasmids and widespread distribution of IncHI2/ST3–blaNDM-5 plasmids across foods, animals, and humans - Lu-Chao Lv; Cheng-Zhen Wang; Jing-Jing Yu; Yan-Xiang Jiao; Li-Min Deng; Wan-Yun He; Guo-Long Gao; Xiao-Yu Zhang; Li-Tao Lu; Xun Gao; Yi-Yun Liu; Jian-Hua Liu (Food Control, 2024)

Experimental and mechanistic studies on the thermo-electric synergistic catalytic oxidation of acetone over MnO2/TiO2-Ni foam catalyst - Chong Tao; Limo He; Xuechen Zhou; Yufan Yang; Hanjian Li; Qiangqiang Ren; Song Hu; Kai Xu; Long Jiang; Jun Xu; Sheng Su; Yi Wang; et al. (Chemical Engineering Journal, 2024)

Gastrodin Regulates PI3K/AKT-Sirt3 Signaling Pathway and Proinflammatory Mediators in Activated Microglia - Han-Jun Zuo; Peng-Xiang Wang; Xue-Qi Ren; Hao-Long Shi; Jin-Sha Shi; Tao Guo; Cheng Wan; Juan-Juan Li (Molecular Neurobiology, 2024)

Geochemical behavior of rare earth elements in agricultural soils along the Syr Darya River within the Aral Sea Basin - Yizhen Li; Galymzhan Saparov; Tao Zeng; Jilili Abuduwaili; Long Ma (Environmental Monitoring and Assessment, 2024)

PI3K/AKT mediated De novo fatty acid synthesis regulates RIG-1/MDA-5-dependent type I IFN responses in BVDV-infected CD8+T cells - Shan-shan Liu; Tong-tong Bai; Tao-lin Que; An Luo; Yu-xin Liang; Yu-xin Song; Tian-yi Liu; Jin-wei Chen; Jing Li; Nan Li; Ze-chen Zhang; Nan-nan Chen; et al. (Veterinary Microbiology, 2024)

Deep leaning in food safety and authenticity detection: An integrative review and future prospects - Yan Wang; Hui-Wen Gu; Xiao-Li Yin; Tao Geng; Wanjun Long; Haiyan Fu; Yuanbin She (Trends in Food Science & Technology, 2024)

Effects of antimicrobial peptides from dietary Hermetia illucens larvae on the growth, immunity, gene expression, intestinal microbiota and resistance to Aeromonas hydrophila of juvenile red claw crayfish (Cherax quadricarinatus) - Ze-Long Zhang; Yong-Qi Meng; Jia-Jun Li; Xiu-Xia Zhang; Jun-Tao Li; Jia-Rui Xu; Pei-Hua Zheng; Jian-An Xian; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

A robust Zr(IV)-based metal-organic framework featuring high-density free carboxylic groups for efficient uranium recovery - Bin Wang; Chunyu Bao; Jiahui Xu; Yunnan Tao; Long Chen; Duo Zhang; Kui Tan; Shuao Wang; Jian-Rong Li; Shengqian Ma (Chemical Engineering Journal, 2024)

Structure-induced interfacial activation convoying the CO-relayed conversion of CO2 to dimethyl carbonate - Shu-Guo Han; Shenghua Zhou; Xiaofang Li; Jianqiang Zhao; Wen-Bo Wei; Lirong Zheng; Dong-Dong Ma; Xin-Tao Wu; Qi-Long Zhu (Chemical Engineering Journal, 2024)

Species distribution modeling combined with environmental DNA analysis to explore distribution of invasive alien mosquitofish (Gambusia affinis) in China - Xu Han; Jinxiao Chen; Lang Wu; Guo Zhang; Xiaoteng Fan; Tao Yan; Long Zhu; Yongjing Guan; Linjun Zhou; Tingting Hou; Xue Xue; Xiangju Li; et al. (Environmental Science and Pollution Research, 2024)

An anomalous rollback process of Mesozoic flat-slab subduction in South China - Bo Yan; Wu-Xian Li; Xiao-Long Huang; Yang Yu; Ji-Hua Tao (Tectonophysics, 2024)

Bio-based ionic liquid filter with enhanced electrostatic attraction for outside filtration and inside collection of viral aerosols - Guo-Hao Zhang; Qiu-Hong Zhu; Lei Zhang; Lei Li; Jie Fu; Shuang-Long Wang; Wen-Li Yuan; Ling He; Guo-Hong Tao (Journal of Hazardous Materials, 2024)

Source identification and exposure risk management for soil arsenic in urban reclamation areas with high background levels: A case study in a coastal reclamation site from the Pearl River Delta, China - Meng Chen; Yuting Zhang; Wenbing Ji; Qiang Chen; Yan Li; Tao Long; Lei Wang (Journal of Hazardous Materials, 2024)

Monospecific and ultrasensitive detection of ofloxacin: A computational chemistry-assisted hapten screening strategy and analysis of molecular recognition mechanism - Jiaxu Xiao; Liangni Qin; Dan Zhao; Niexie Huang; Wennuo Xu; Linwei Zhang; Xiaoming Pan; Shiyun Han; Mingyue Ding; Long Li; Tao Le; Dapeng Peng (Journal of Hazardous Materials, 2024)

Temporal dynamics of plant−soil feedback and related mechanisms depend on environmental context during invasion processes of a subtropical invader - Yang-Ping Li; Wei-Tao Li; Ju Li; Yu-Long Feng (Plant and Soil, 2024)

Quantitative Proteomic and Phosphoproteomic Analyses Reveal a Role of Death-Associated Protein Kinase 1 in Regulating Hippocampal Synapse - Yuan Tian; Xiaoqing Zheng; Ruomeng Li; Li Hu; Xindong Shui; Long Wang; Dongmei Chen; Tae Ho Lee; Tao Zhang (Molecular Neurobiology, 2024)

Astronomical forcing and sedimentary noise modeling of lake-level changes in the Middle Eocene Chezhen Sag, Bohai Bay Basin, eastern China - Xuwei Luan; Jinliang Zhang; Na Li; Tao Chen; Long Sun; Xuecai Zhang (Frontiers of Earth Science, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Application of roadside air purifiers in urban street canyons: A pilot-scale study in Hong Kong - Xinwei Li; Shuwen Han; Pengge Wang; Han Mei; Zhi Ning; Fan Dong; Long Cui; Yu Huang; Tao Wang; Shao-Yuan Leu; Meng Wang; Shun-cheng Lee (Science of The Total Environment, 2024)

High-temperature interaction mechanisms of typical igniting pyrotechnics with cellulose as the packing material - Xiao-Tao Tian; Yu-Xue Li; Ming-Hui Yu; Bing Xiao; Pei-Jin Liu; Qi-Long Yan (Fuel, 2024)

Effects of dietary astaxanthin on growth performance, muscle composition, non-specific immunity, gene expression, and ammonia resistance of juvenile ivory shell (Babylonia areolate) - Teng Li; Pei-Hua Zheng; Xiu-Xia Zhang; Ze-Long Zhang; Jun-Tao Li; Jia-Jun Li; Jia-Rui Xu; Dong-Mei Wang; Jian-An Xian; Hui Guo; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

Effects of dietary chitosan oligosaccharide on the growth, intestinal microbiota and immunity of juvenile red claw crayfish (Cherax quadricarinatus) - Ze-Long Zhang; Yan-Lei Cao; Jia-Rui Xu; Xiu-Xia Zhang; Jia-Jun Li; Jun-Tao Li; Pei-Hua Zheng; Jian-An Xian; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

Optimization analysis of thermal–hydraulic features of the 2.5 MW LBE spallation target of CiADS - Weiping Deng; Tao Wan; Weifeng Yang; Yongqin Ju; Fei Ma; Chengwen Qiang; Long Li; Fei Wang; Xueying Zhang (Annals of Nuclear Energy, 2024)

A pair of new chromone enantiomers from Xylaria nigripes - Jing Li; Yue-Ping Jiang; Lan-Qing Li; Hong-Ping Long; Hai-Tao Liu; Rong Yang; Shao Liu; Wen-Xuan Wang; Ji-Kai Liu (Natural Product Research, 2024)

Sirtuin 3-mediated deacetylation of superoxide dismutase 2 ameliorates sodium fluoride-induced mitochondrial dysfunction in porcine oocytes - Xin-Yue Qi; Jin-Dong Yuan; Zi-Yu Liu; Xi-Qing Jiang; Qi Zhang; Shan-Long Zhang; Lu Zhao; Ling-Yan Ke; Chen-Yuan Zhang; Yan Li; Lu-Yan Zhang; Qian-Qian Xu; et al. (Science of The Total Environment, 2024)

Exploring strength deterioration mechanism of soil-rock mixture based on pore structure characteristics under freeze–thaw cycles - Liyun Tang; Zihan Lu; Tao Zhao; Zhuo Li; Peiyong Qiu; Yongtang Yu; Long Jin; Yongqiang Li; Hailiang Jia (Cold Regions Science and Technology, 2024)

Potentiation of the lateral habenula-ventral tegmental area pathway underlines the susceptibility to depression in mice with chronic pain - Chun-Kui Zhang; Pan Wang; Yuan-Yuan Ji; Jian-Shuai Zhao; Jun-Xiang Gu; Xian-Xia Yan; Hong-Wei Fan; Ming-Ming Zhang; Yu Qiao; Xiao-Die Liu; Bao-Juan Li; Ming-Hui Wang; et al. (Science China Life Sciences, 2024)

The phosphoproteome is a first responder in tiered cellular adaptation to chemical stress followed by proteomics and transcriptomics alteration - Peiru Chen; Yuan Li; Qi Long; Tao Zuo; Zhenpeng Zhang; Jiabin Guo; Danyang Xu; Kaixuan Li; Shu Liu; Suzhen Li; Jian Yin; Lei Chang; et al. (Chemosphere, 2023)

Buoyancy-driven natural ventilation performance of a multi-story building with vertical shaft designed by using dimensionless design approach - Xuhui Shi; Yongcai Li; Tianhe Long; Ningjing Zhao; Shuli Liu; Tao Li (Sustainable Cities and Society, 2023)

Can microplastics and disinfectant resistance genes pose conceivable threats to water disinfection process? - Maocai Shen; Yifei Zhao; Shiwei Liu; Shiyu Tao; Tianhao Li; Hongming Long (Science of The Total Environment, 2023)

Transport of pollutants in groundwater of domestic waste landfills in karst regions and its engineering control technologies - Bo Li; Teng Li; Pan Wu; Lei Yang; Jie Long; Pu Liu; Tao Li (Journal of Environmental Management, 2023)

Allyl methyl disulfide (AMDS) prevents N,N-dimethyl formamide-induced liver damage by suppressing oxidative stress and NLRP3 inflammasome activation - Long-Xia Li; Lin Wang; Shuo Wang; Xiu-Ning Zhang; Hong Liu; Yan-Jing Zhang; Chuan-Tao Wu; Cui-Li Zhang; Tao Zeng (Food and Chemical Toxicology, 2023)

Black carbon, soil organic matter molecular signatures under different land uses in Shenyang, China and relationship with PAHs - Han Gao; Huixin Li; Jiaqi Shi; Jianbo Huang; Jing Wei; Xiaolei Qu; Tao Long (Chemosphere, 2023)

Proteomic analysis of EPC cell replication effect of Hsp70 on SVCV infection at different temperatures - Xue Jiao; Long-tao Wang; Ai-dong Qian; Yue-hong Li (Aquaculture, 2023)

Monoterpenoids from the root bark of Acanthopanax gracilistylus and their inhibitory effects on neutrophil elastase, 5-lipoxygenase, andcyclooxygenase-2 in vitro - Hao-Dong Yang; Zhi-Shu Tang; Tao-Tao Xue; Huai-Li Xu; Bao-Long Hou; Ya-Ya Zhu; Zeng-Hu Su; Hong-Bo Xu (Phytochemistry, 2023)

Effect of low molecular weight organic acids on the lead and chromium release from widely-used lead chromate pigments under sunlight irradiation - Han Gao; Huixin Li; Xinwei Zhou; Jing Wei; Xiaolei Qu; Tao Long (Environmental Pollution, 2023)

Sources of antimony contamination and its migration into water systems of Xikuangshan, China: Evidence from hydrogeochemical and stable isotope (H, O, S, and Sr) signatures - Bing Wen; Aiguo Zhou; Jianwei Zhou; Jianbo Huang; Tao Long; Xiaocen Jia; Weiqing Zhou; Wanyu Li (Environmental Pollution, 2023)

Utilizing internal resonant scattering to improve photoluminescence energy outcoupling of CsPbBr3/Cs4PbBr6 perovskite phosphor - Zong-Tao Li; Bo-Jia Li; Jia-Sheng Li; Cun-Jiang Song; Xin-Rui Ding; Hai-Long Yuan; Bin-Hai Yu; Yong Tang; Jian-Zhen Ou; Romain Gautier; Hong-Lei Ji; Hao-Chung Kuo (Chemical Engineering Journal, 2023)

Locating the Scope and Depth of Coal Fires Based on Magnetic and Electrical Data - Zhenlu Shao; Guofu Zhang; Tao Zhou; Jun Wei; Fei Cao; Yong Zhang; Hongsheng Li; Huahai Sun; Shangkun Qing; Teng Chen; Long Chen; Hongwen Shao; et al. (Pure and Applied Geophysics, 2023)

Short-term effect of meteorological factors and extreme weather events on daily outpatient visits for dry eye disease between 2013 and 2020: a time-series study in Urumqi, China - Si-Yu Gui; Fei Wang; Jian-Chao Qiao; Xin-Chen Wang; Zhi-Hao Huang; Fan Yang; Cheng-Yang Hu; Fang-Biao Tao; Li-Ming Tao; Dong-Wei Liu; Xiang-Long Yi; Zheng-Xuan Jiang (Environmental Science and Pollution Research, 2023)

Associating phthalate exposure during pregnancy with preschooler's FMI, ABSI and BRI trajectories via putative mechanism pathways - Hui Gao; Yi Zhang; Li-wen Chen; Hong Gan; Meng-juan Lu; Binbin Huang; Juan Tong; Meng-long Geng; Kun Huang; Cheng Zhang; Bei-bei Zhu; Shan-shan Shao; et al. (Chemosphere, 2023)

Assessing the suitability of three purple soils for aquaculture by physiological responses in freshwater bivalves (Hyriopsis cumingii) - Qinglin Yang; Jing Mei; Xiaoqi Tang; Tao Wang; Kai Long; Yang Liu; Yanhong Li; Xiaobo Yu; Weizhi Yao; Zhengli Wu (Aquaculture, 2023)

Collision avoidance fault-tolerant control for dynamic positioning vessels under thruster faults - Ming-Yang Li; Long-Tao Liu; Wen-Bo Xie; Ji-Tao Li (Ocean Engineering, 2023)

Phosphoproteome reveals long-term potentiation deficit following treatment of ultra-low dose soman exposure in mice - Qi Long; Zhenpeng Zhang; Yuan Li; Yuxu Zhong; Hongyan Liu; Lei Chang; Ying Ying; Tao Zuo; Yong'an Wang; Ping Xu (Journal of Hazardous Materials, 2023)

New insights into the regulation mechanism of Pacific white shrimp (Litopenaeus vannamei) hepatopancreas under 4-nonylphenol exposure using transcriptome analysis - Pei-Hua Zheng; Yao-Peng Lu; Xiu-Xia Zhang; Ke-Er Luan; Ze-Long Zhang; Jia-Jun Li; Tong Xu; Jun-Tao Li; Jian-An Xian; Hui Guo; An-Li Wang (Fish & Shellfish Immunology, 2023)

Elemental sulfur autotrophic partial denitrification (S0-PDN) with high pH and free ammonia control strategy for low-carbon wastewater: From performance to microbial mechanism - Yong Li; Bohan Chen; Xiaolei Zhang; Zhizhan Luo; Mengen Lei; Tao Song; Zhiyun Long; Ji Li; Jun Ma (Chemical Engineering Journal, 2023)

LncRNA XIST Exacerbates Oxygen-Glucose Deprivation/Reoxygenation-Induced Cerebral Injury Through the miR-25-3p/TRAF3 Axis - You Li; Ji-Kun Zhang; Zheng-Tao Yu; Jun-Wen Jiang; Hong Tang; Guo-Long Tu; Ying Xia (Molecular Neurobiology, 2023)

The effect of acid rain and fertilization on the performance of invasive Chromolaena odorata and two native plants - Yan-mei Liu; Wei-tao Li; Yu-long Zheng (Acta Oecologica, 2023)

Metformin improves sheep sperm cryopreservation via vitalizing the AMPK pathway - Xing Zhang; Song-Mao Guo; Da-Wei Zhu; Yu Li; Fei Wen; Ming Xian; Zhang-Tao Hu; Qian-Long Zou; Li-Kun Zhang; Yu-Lin Chen; Jian-Hong Hu (Theriogenology, 2023)

Toxic effects of perfluorocaproic acid (PFHxA) on crucian carp (Carassius auratus) and the response of the intestinal microbial community - Xue Jiao; Zheng yao Guo; Bing li Liu; Long tao Wang; Zhi nan Yang; Yuan ru Yang; Ai-dong Qian; Yue-hong Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Anti-apoptotic effect of adrenomedullin gene delivery on Leydig cells by suppressing TGF-β1 via the Hippo signaling pathway - You-wen Luo; Xia-lian Zhu; Ming-yong Li; Jian-hua Zhou; Zhi-min Yang; Tao Tong; Bing-hai Chen; Song-lin Qin; Bo-long Liu; Wei Hu (Reproductive Toxicology, 2023)

A sensitive and specific enzyme-linked immunosorbent assay for the detection of pymetrozine in vegetable, cereal, and meat - Xiaoyang Yin; Huaming Li; Shuangmin Wu; Yanrong Lu; Yalin Yang; Liangni Qin; Long Li; Jiaxu Xiao; Jixiang Liang; Yu Si; Tao Le; Dapeng Peng (Food Chemistry, 2023)

Identification and expression characteristics of NLP (NIN-like protein) gene family in pepper (Capsicum annuum L.) - Yuan Wu; Shi-xian Su; Tao Wang; Gui-Hua Peng; Lei He; Cha Long; Wei Li (Molecular Biology Reports, 2023)

Effect of liver metastasis on the efficacy of immune checkpoint inhibitors in cancer patients: a systemic review and meta-analysis - Bao-Wen Tian; Cheng-Long Han; Han-Chao Wang; Lun-Jie Yan; Zi-Niu Ding; Hui Liu; Xin-Cheng Mao; Jin-Cheng Tian; Jun-Shuai Xue; Long-Shan Yang; Si-Yu Tan; Zhao-Ru Dong; et al. (Clinical & Experimental Metastasis, 2023)

Dual-drug loaded polysaccharide-based self-healing hydrogels with multifunctionality for promoting diabetic wound healing - Weiwei Tan; Tao Long; Yanzhuo Wan; Bingchen Li; Zhilang Xu; Lei Zhao; Changdao Mu; Liming Ge; Defu Li (Carbohydrate Polymers, 2023)

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

Spatiotemporal characteristics and dynamic risk assessment of a multi-solvents abandoned pesticide-contaminated site with a long history, in China - Mengjie Wang; Dengdeng Jiang; Da Ding; Shaopo Deng; Lingya Kong; Jing Wei; Feiyang Xia; Mei Li; Tao Long (Journal of Environmental Management, 2023)

Mesoporous zeolite Beta supported Ni nanoparticles for the catalytic hydroconversion of extraction portion from Jinjitan subbituminous coal to cycloalkanes - Juan Gao; Xian-Yong Wei; Yu-Hong Kang; Xiao-Qi Zhang; Ai-Min Wang; Xia-Long Li; Yong Gao; Guang-Hui Liu; Tao Chen; Yan-Jun Li; Xiang-Rong Ma; Jin-Jun Bai; et al. (Fuel, 2023)

Reliable spectroscopic identification of minerals associated with serpentinization: Relevance to Mars exploration - Wen-Ping Liu; Wei Yin; Bin-Long Ye; Tian-Lei Zhao; Qi-Zhi Yao; Yi-Liang Li; Sheng-Quan Fu; Gen-Tao Zhou (Icarus, 2023)

Cl modulation on boron-rich carbon embedded with NiFe alloys for efficient oxygen evolution reaction - Jiateng Li; Kaitian Zheng; Chi Zhang; Long Jiao; Zhiheng Dong; Xinyue Tao; Rui Su; Haijiao Xie; Chunjian Xu (Chemical Engineering Journal, 2023)

Click-crosslinked in-situ hydrogel improves the therapeutic effect in wound infections through antibacterial, antioxidant and anti-inflammatory activities - Xiong-Xin Lei; Chen-Yu Zou; Juan-Juan Hu; Yan-Lin Jiang; Xiu-Zhen Zhang; Long-Mei Zhao; Tao He; Qing-Yi Zhang; Ya-Xing Li; Jesse Li-Ling; Hui-Qi Xie (Chemical Engineering Journal, 2023)

Production of MSTN knockout porcine cells using adenine base-editing-mediated exon skipping - Shuai-peng Yang; Xiang-xing Zhu; Zi-xiao Qu; Cai-yue Chen; Yao-bing Wu; Yue Wu; Zi-dan Luo; Xin-yi Wang; Chu-yu He; Jia-wen Fang; Ling-qi Wang; Guang-long Hong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2023)

Purification and biochemical characterization of a novel ene- reductase from Kazachstania exigua HSC6 for dihydro-β-ionone from β-ionone - Zhangde Long; Kena Li; Yun Xue; Yongwei Sun; Jigang Li; Zan Su; Jiansheng Sun; Qibin Liu; Hong Liu; Tao Wei (Biotechnology Letters, 2023)

Root exudation processes induce the utilization of microbial-derived components by rhizoplane microbiota under conservation agriculture - Yüze Li; Mei Long; Yuting Hou; Wei Li; Xiaoliang Qin; Baogang Zhang; Tao Wen; Yongxing Cui; Ziting Wang; Yuncheng Liao (Soil Biology and Biochemistry, 2023)

A quantum algorithm for heat conduction with symmetrization - Shi-Jie Wei; Chao Wei; Peng Lv; Changpeng Shao; Pan Gao; Zengrong Zhou; Keren Li; Tao Xin; Gui-Lu Long (Science Bulletin, 2023)

Evidence of hydrothermal fluid migration pathways in pores and microfractures based on nuclear magnetic resonance and electron microscopic analyses from the Southwest Indian Ridge - Qianyu Li; Chao Chen; Chunhui Tao; Tao Wu; Jianping Zhou; Zhaoyang Su; Zhongmin Zhu; Long Liu; Tianyu Jie; Ming Chen (Marine Geology, 2023)

Petrogenesis of the Chakabeishan pegmatites, North Qaidam Terrane: Implications for Indosinian lithium mineralization in the northern Tibetan Plateau - Jin-Heng Liu; Qiang Wang; Bing-Zhang Wang; Wu-Fu Li; Chuan-Bing Xu; Shan-Ping Li; Zi-Long Wang; Lu-Lu Hao; Tai-Zhong Song; Chun-Tao Wang; Ying Zheng; Jin-Shou Wang (Lithos, 2023)

β‐diversity in temperate grasslands is driven by stronger environmental filtering of plant species with large genomes - Hai‐Yang Zhang; Xiao‐Tao Lü; Cun‐Zheng Wei; Jeff R. Powell; Xiao‐Bo Wang; Ding‐Liang Xing; Zhu‐Wen Xu; Huan‐Long Li; Xing‐Guo Han (Ecology, 2023)
Elucidating mechanisms underlying community assembly and biodiversity patterns is central to ecology and evolution. Genome size (GS) has long been hypothesized to potentially affect species' capacity to tolerate environmental stress and might therefore help drive community assembly. However, its role in driving β‐diversity (i.e., spatial variability in species composition) remains unclear. We measured GS for 161 plant species and community composition across 52 sites spanning a 3200‐km transect in the temperate grasslands of China. By correlating the turnover of species composition with environmental dissimilarity, we found that resource filtering (i.e., environmental dissimilarity that includes precipitation, and soil nitrogen and phosphorus concentrations) affected β‐diversity patterns of large‐GS species more than small‐GS species. By contrast, geographical distance explained more variation of β‐diversity for small‐GS than for large‐GS species. In a 10‐year experiment manipulating levels of water, nitrogen, and phosphorus, adding resources increased plant biomass in species with large GS, suggesting that large‐GS species are more sensitive to the changes in resource availability. These findings highlight the role of GS in driving community assembly and predicting species responses to global change.

Contaminant characterization at pesticide production sites in the Yangtze River Delta: Residue, distribution, and environmental risk - Mei Li; Qiang Chen; Lu Yang; Ya Zhang; Jinlin Jiang; Shaopo Deng; Jinzhong Wan; Tingting Fan; Tao Long; Shengtian Zhang; Yusuo Lin (Science of The Total Environment, 2023)

A disease-specific spectral index tracks Magnaporthe oryzae infection in paddy rice from ground to space - Long Tian; Ziyi Wang; Bowen Xue; Dong Li; Hengbiao Zheng; Xia Yao; Yan Zhu; Weixing Cao; Tao Cheng (Remote Sensing of Environment, 2023)

Progress and trend of minimum quantity lubrication (MQL): A comprehensive review - Tao He; Niancong Liu; Huazheng Xia; Long Wu; Yu Zhang; Daigang Li; Yun Chen (Journal of Cleaner Production, 2023)

Breakage-resistant hydrogel electrode enables ultrahigh mechanical reliability for triboelectric nanogenerators - Rui Li; Zhenyu Xu; Long Li; Junjie Wei; Wenqin Wang; Zejun Yan; Tao Chen (Chemical Engineering Journal, 2023)

Default mode network mechanisms of repeated transcranial magnetic stimulation in heroin addiction - Long Jin; Menghui Yuan; Wei Zhang; Lei Wang; Jiajie Chen; Fan Wang; Jia Zhu; Tao Liu; Yixin Wei; Yunbo Li; Wei Wang; Qiang Li; et al. (Brain Imaging and Behavior, 2023)

New azaphilones from mangrove endophytic fungus Penicillium sclerotiorin SCNU-F0040 - Jialin Li; Zixuan Li; Tao Chen; Geting Ye; Liyu Qiu; Yuhua Long (Natural Product Research, 2023)

Interannual and seasonal relationships between photosynthesis and summer soil moisture in the Ili River basin, Xinjiang, 2000–2018 - Tao Yu; Guli Jiapaer; Gang Long; Xu Li; Jingyu Jing; Ying Liu; Philippe De Maeyer; Tim Van de Voorde (Science of The Total Environment, 2023)

New insights into the regulation mechanism of red claw crayfish (Cherax quadricarinatus) hepatopancreas under air exposure using transcriptome analysis - Yao-Peng Lu; Pei-Hua Zheng; Xiu-Xia Zhang; Jun-Tao Li; Ze-Long Zhang; Jia-Rui Xu; Yong-Qi Meng; Jia-Jun Li; Jian-An Xian; An-Li Wang (Fish & Shellfish Immunology, 2023)

Heteroaggregation effects on Pickering stabilization using oppositely charged cellulose nanocrystal and nanochitin - Shasha Guo; Ya Zhu; Wenyang Xu; Siqi Huan; Jun Li; Tao Song; Long Bai; Orlando J. Rojas (Carbohydrate Polymers, 2023)

Effects of Dietary Eucommia ulmoides Leaf Extract on Growth, Muscle Composition, Hepatopancreas Histology, Immune Responses and Microcystin-LR Resistance of Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Yao-Peng Lu; Pei-Hua Zheng; Jia-Rui Xu; Yan-Lei Cao; Jun-Tao Li; Chen-Guang Hao; Ze-Long Zhang; Jian-An Xian; Xiu-Xia Zhang; An-Li Wang (Fishes, 2022)
The objective of the present study was to investigate the effects of different doses of dietary Eucommia ulmoides leaf extract (ELE) on juvenile red claw crayfish (Cherax quadricarinatus). A total number of 720 red claw crayfish (initial body weight of 0.24 ± 0.01 g) were randomly assigned to six groups and fed diets containing 0 (Diet 1), 0.5 (Diet 2), 1 (Diet 3), 2 (Diet 4), 4 (Diet 5) and 10 (Diet 6) g dry weight (dw) ELE kg (dw)−1 diets for eight weeks and challenged with microcystin-LR stress. The results indicated that dietary supplementation with 1–2 g dw ELE kg (dw)−1 diet could significantly improve the weight gain rate (WGR) and specific growth rate (SGR) of crayfish. Muscle crude protein contents of crayfish fed Diet 2, Diet 3, and Diet 4 were significantly higher than those of the control group. Compared with the control group, dietary ELE could increase total antioxidant capacity (T-AOC), superoxide dismutase (SOD), glutathione peroxidase (GPx), acid phosphatase (ACP), alkaline phosphatase (AKP), and phenoloxidase (PO) activities and decrease malondialdehyde (MDA) level of crayfish. Dietary ELE significantly increased the relative expression levels of SOD, thioredoxin 1 (TRX1), GPx, selenium-dependent glutathione peroxidase (Se-GPx), cytochrome P450 (CYP450), anti-lipopolysaccharide factor (ALF) and C-type lysozyme (C-LZM) mRNA of crayfish compared with the control group during the feeding experiment. When subjected to MC-LR stress for 48 h, the mRNA expression levels of SOD, GPx, Se-GPx, glutathione-s-transferase 1 (GST1), ALF, hemocyanin (HEM), and C-LZM in the hepatopancreas could be improved to varying degrees compared with the Diet 1. Supplementation of 1–2 g dw ELE kg (dw)−1 diet could improve the survival rate (SR) of crayfish under MC-LR stress. These results indicated that dietary ELE (1–2 g dw ELE kg (dw)−1 diet) could improve the growth performance, muscle protein, and non-specific immune response and increase the SR of crayfish under MC-LR stress by regulating the mRNA expression levels of the immune- and antioxidant-related genes.

Selenium attenuates the association of co-exposure to arsenic, cadmium, and lead with cognitive function among Chinese community-dwelling older adults - Bei-Jing Cheng; Jie Sheng; Hong-Li Wang; Yuan Wang; Hong-Juan Cao; Xiu-De Li; Ting-Ting Zhou; Xiang-Long Meng; Huan-Huan Nie; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; et al. (Environmental Science and Pollution Research, 2022)

Honokiol Reduces Mitochondrial Dysfunction and Inhibits Apoptosis of Nerve Cells in Rats with Traumatic Brain Injury by Activating the Mitochondrial Unfolded Protein Response - Guang-wei Sun; Tian-yi Ding; Meng Wang; Chang-long Hu; Jiang-jiang Gu; Jie Li; Tao Qiu (Journal of Molecular Neuroscience, 2022)

The association between essential trace element mixture and atherosclerotic cardiovascular disease risk among Chinese community-dwelling older adults - Xiang-long Meng; Yuan Wang; Hong-li Wang; Huan-huan Nie; Bei-jing Cheng; Hong-juan Cao; Xiu-de Li; Su-fang Wang; Gui-mei Chen; Fang-biao Tao; Jie Sheng; Lin-sheng Yang (Environmental Science and Pollution Research, 2022)

Gender-specific effects of prenatal mixed exposure to serum phthalates on neurodevelopment of children aged 2–3 years:the Guangxi Birth Cohort Study - Yuan Zheng; Longman Li; Hong Cheng; Shengzhu Huang; Xiuming Feng; Lulu Huang; Luyun Wei; Dehao Cao; Sida Wang; Long Tian; Weijun Tang; Caitong He; et al. (Environmental Science and Pollution Research, 2022)

Cadmium Through Disturbing MTF1-Mediated Metal Response Induced Cerebellar Injury - Shao-Shuai Bi; Milton Talukder; Hai-Tao Jin; Mei-Wei Lv; Jing Ge; Cong Zhang; Jin-Long Li (Neurotoxicity Research, 2022)

Genetic and transcriptomic dissection of an artificially induced paired spikelets mutant of wheat (Triticum aestivum L.) - Juanyu Zhang; Yanyan Tang; Xi Pu; Xuebing Qiu; Jinhui Wang; Tao Li; Zhao Yang; Yao Zhou; Yuxiao Chang; Junjun Liang; Haili Zhang; Guangbing Deng; et al. (Theoretical and Applied Genetics, 2022)

Influence of asymmetric blockage of the drainage system of a deep-buried tunnel on water gushing - He-lin Fu; Peng-tao An; Yi-min Wu; Jie Li; Long Chen (Journal of Mountain Science, 2022)

Amelioration of Flesh Quality in Hybrid Grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatu) Fed With Oxidized Fish Oil Diet by Supplying Lactobacillus pentosus - Xiaobo Yan; Simiao Pan; Zhihao Li; Xiaohui Dong; Beiping Tan; Shuisheng Long; Tao Li; Xiangxiang Suo; Yuanzhi Yang (Frontiers in Marine Science, 2022)
The objective was to investigate the improvement of the flesh quality and nutritional value of hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatu ) by Lactobacillus pentosus (BL-15). The two diets were prepared with 9% oxidized fish oil (OFO negative control group) or 9% fresh fish oil (FFO positive control group) as the major lipid source, and the OFO diet were sprayed with L. pentosus at 1.0×10 7 , 1.0×10 8 , 1.0×10 9 CFU/g, respectively. Five kinds of diets were fed to hybrid grouper with initial weight of 21.36 ± 0.03 g for 60 days. The results showed that (1) consumption of OFO diet significantly increased muscle crude lipid, total cholesterol, and total monounsaturated fatty acids contents and significantly decreased muscle C20:5n3, C22:6n3, ∑PUFA levels of grouper ( p < 0.05), whereas the addition of L. pentosus to OFO diet significantly reduced muscle crude lipid, malondialdehyde, reactive oxygen radicals, total cholesterol concentration, increased C20:5n3, C22:6n3, ∑PUFA levels, increased muscle crude protein content, and enhanced muscle hardness, gumminess, and chewiness compared with FFO or OFO group ( p < 0.05). (2) In addition, ingestion of OFO diet significantly increased muscle phenylalanine content and significantly decreased aspartic acid content ( p < 0.05), while the addition of L. pentosus restored aspartic acid to the level not significantly different from that of FFO group ( p > 0.05). The addition of L. pentosus also increased tyrosine, lysine, leucine, phenylalanine, arginine, and alanine content compared to FFO group at the same time ( p < 0.05). (3) Furthermore, the intake of OFO diet would lead to deterioration in muscle flavor quality and increase in noxious odors in grouper, and the addition of L. pentosus can mitigate or rectify these detrimental consequences. In further analysis, consumption of OFO group significantly downregulated the mRNA expression of muscle growth factors and caused serious damage to the muscle antioxidant system ( p < 0.05), which was protected against by the potent antioxidant properties of L. pentosus . We recommend the supplementation level of L. pentosus to be 1.0×10 9 CFU/g under the highly oxidized conditions of the present trial fish oil.

Effect of GLP-1R rs2254336 and rs3765467 polymorphisms on gastrointestinal adverse reactions in type 2 diabetes patients treated with liraglutide - Jiangchuan Long; Yongjian Liu; Yaqian Duan; Yang Li; Gangyi Yang; Ziyu Ren; Wei Tao; Dongfang Liu (European Journal of Clinical Pharmacology, 2022)

Sex-specific mediation of placental inflammatory biomarkers in the effects of prenatal phthalate coexposure on preschooler cognitive development - Hui Gao; Juan Tong; Bei-bei Zhu; Meng-long Geng; Hong Gan; Li Sun; Xiao-yan Wu; Kun Huang; Hui Cao; Wen-wen Liu; Shu-man Tao; Peng Ding; et al. (Environmental Science and Pollution Research, 2022)

Genetic dissection of quantitative trait loci for grain size and weight by high-resolution genetic mapping in bread wheat (Triticum aestivum L.) - Tao Li; Guangbing Deng; Yan Su; Zhao Yang; Yanyan Tang; Jinhui Wang; Juanyu Zhang; Xvebing Qiu; Xi Pu; Wuyun Yang; Jun Li; Zehou Liu; et al. (Theoretical and Applied Genetics, 2022)

Standard litterbags underestimate early-stage lower-order root decomposition rate in a subtropical forest, China - Guan-tao Chen; Yu-qin Chen; Yong Peng; Hong-ling Hu; Jiu-long Xie; Gang Chen; Yin-long Xiao; Li Liu; Yi Tang; Li-hua Tu (Plant and Soil, 2021)

A novel thermophilic β-carotene 15,15′-monooxygenase with broad substrate specificity from the marine bacterium Candidatus Pelagibacter sp. HTCC7211 - Zhangde Long; Yuzhe Zhao; Yun Xue; Min Wang; Jigang Li; Zan Su; Jiansheng Sun; Qibin Liu; Hong Liu; Duobin Mao; Tao Wei (Biotechnology Letters, 2021)

Research on support method in soft rock tunnel considering the rheological characteristics of rock - Xiao-long Guo; Yong-quan Zhu; Zhong-sheng Tan; Lei Li; Ang Li; Ya-tao Yan (Arabian Journal of Geosciences, 2021)

The Effect of Oxidized Fish Oil on the Spleen Index, Antioxidant Activity, Histology and Transcriptome in Juvenile Hybrid Grouper (♀ Epinephelus fuscoguttatus × ♂ Epinephelus lanceolatus) - Shuisheng Long; Zhihao Li; Xiaohui Dong; Xiaobo Yan; Hao Liu; Beiping Tan; Shuang Zhang; Simiao Pan; Tao Li; Xiangxiang Suo; Yuanzhi Yang (Frontiers in Marine Science, 2021)
The spleen is an important organ in the immune function of fish, and it is also important for hematogenesis and antibody and granulocyte production. However, the effect of oxidized fish oil on the spleen of hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ Epinephelus lanceolatus ) is unknown. In this study, hybrid groupers were fed with oxidized fish oil and the spleen index, antioxidant ability, histology and transcriptome were investigated. Oxidized fish oil did not affect the spleen index. Levels of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px) and malondialdehyde (MDA) in the spleen were significantly increased as the amount of oxidized fish oil in the diet increased, but the vitamin E concentration was significantly decreased. The morphological organization of the spleen was damaged with increased oxidative stress. And the spleen reacted to oxidative stress by platelet activation, FOXO and notch signaling pathways, which involved amyloid beta precursor protein binding family B member 1 interacting protein (APBB1IP) gene, glucose-6-phosphatase (G6PC) gene, histone acetyltransferase p300 (EP300) gene, insulin gene and notch 2 gene. In conclusion, the oxidized fish oil caused oxidative stress and damaged its structure. Additionally, oxidized fish oil changed the transcription profile of the spleen.

Identification and validation of two major QTLs for spike compactness and length in bread wheat (Triticum aestivum L.) showing pleiotropic effects on yield-related traits - Tao Li; Guangbing Deng; Yan Su; Zhao Yang; Yanyan Tang; Jinhui Wang; Xvebing Qiu; Xi Pu; Jun Li; Zehou Liu; Haili Zhang; Junjun Liang; et al. (Theoretical and Applied Genetics, 2021)

How light affect the magnetotactic behavior and reproduction of ellipsoidal multicellular magnetoglobules? - Xinxin Qian; Yicong Zhao; Claire-Lise Santini; Hongmiao Pan; Tian Xiao; Haitao Chen; Tao Song; Jinhua Li; Francois Alberto; Sophie Brustlein; Long-Fei Wu (Journal of Oceanology and Limnology, 2021)

Oceanic vertical mixing of the lower halocline water in the Chukchi Borderland and Mendeleyev Ridge - Long Lin; Hailun He; Yong Cao; Tao Li; Yilin Liu; Mingfeng Wang (Acta Oceanologica Sinica, 2021)

Genetic and molecular characterization of determinant of six-rowed spike of barley carrying vrs1.a4 - Jin-Hui Wang; Zhen-Mei Xu; Xue-Bing Qiu; Li-Lan Li; Shui-Yang Yu; Tao Li; Yan-Yan Tang; Xi Pu; Juan-Yu Zhang; Hai-Li Zhang; Jun-Jun Liang; Ya-Wei Tang; et al. (Theoretical and Applied Genetics, 2021)

Genomic and transcriptomic insights into the habitat adaptation of the diazotrophic paddy‐field cyanobacterium Nostoc sphaeroides - Zhen Chen; Jin‐Long Shang; Shengwei Hou; Tao Li; Qi Li; Yi‐Wen Yang; Wolfgang R. Hess; Bao‐Sheng Qiu (Environmental Microbiology, 2021)
Summary Nitrogen‐fixing cyanobacteria are common in paddy fields, one of the most productive wetland ecosystems. Here, we present the complete genome of Nostoc sphaeroides, a paddy‐field diazotroph used for food and medicine for more than 1700 years and deciphered the transcriptional regulation during the developmental transition from hormogonia to vegetative filaments with heterocysts. The genome of N. sphaeroides consists of one circular chromosome (6.48 Mb), one of the largest ever reported megaplasmids (2.34 Mb), and seven plasmids. Multiple gene families involved in the adaption to high solar radiation and water fluctuation conditions were found expanded, while genes involved in anoxic adaptation and phosphonate utilization are located on the megaplasmid, suggesting its indispensable role in environmental adaptation. Distinct gene expression patterns were observed during the light‐intensity‐regulated transition from hormogonia to vegetative filaments, specifically, genes encoding proteins involved in photosynthetic light reaction, carbon fixation, nitrogen metabolism and heterocyst differentiation were significantly upregulated, whereas genes related to cell motility were down‐regulated. Our results provide genomic and transcriptomic insights into the adaptation of a filamentous nitrogen‐fixing cyanobacterium to the highly dynamic paddy‐field habitat, suggesting N. sphaeroides as an excellent system to understand the transition from aquatic to terrestrial habitats and to support sustainable rice production.

Contributions of natural climate variability on the trends of seasonal precipitation extremes over China - Fuqiang Cao; Tao Gao; Li Dan; Fengxia Zhao; Xiang Gong; Xinyu Zhang; Xiaoyu Long; Junjie Zhan (International Journal of Climatology, 2021)
The increased trends of extreme precipitation events over China have been partially attributed to global warming, while it is unclear how the natural climate variability affect these variations in extreme rainfall trends. Here we examine the contributions of large‐scale modes climate variability from the Pacific Ocean, which are represented by El Niño‐Southern Oscillation (ENSO) and Pacific Decadal Oscillation (PDO), on the trends of seasonal extreme events across China. Results show that the effects of climate variability modes on precipitation extremes exhibit evidently spatiotemporal characteristics at the seasonal scale. A significant positive trend is found over southeastern and northwestern China in four seasons, and substantial increases in two types of extreme events are also seen over northwestern China in spring and winter. Most of the seasonal trends of extreme precipitation events can be explained by the trends of the principal components. El Niño (La Niña) and PDO–like sea surface temperature (SST) anomalies over the Pacific have a close linkage with the variations in precipitation extremes. By modulating the large‐scale atmospheric circulations, these Pacific SST anomalies associated with climatic oscillations, such as ENSO and PDO, provide the conducive conditions responsible for the occurrences of seasonal precipitation extremes across China. The seasonal trends of extreme events can be largely explained by the variability of the ENSO and PDO episodes, with a relatively larger modulation of PDO as compared to ENSO. These researches have important implications for improving seasonal flood disaster predictability and climate model performances.

Identification and candidate gene mining of HvSS1, a novel qualitative locus on chromosome 6H, regulating the uppermost internode elongation in barley (Hordeum vulgare L.) - Xi Pu; Yanyan Tang; Meihao Zhang; Tao Li; Xvebing Qiu; Juanyu Zhang; Jinhui Wang; Lilan Li; Zhao Yang; Yan Su; Haili Zhang; Junjun Liang; et al. (Theoretical and Applied Genetics, 2021)

The resurgent landscape of xenotransplantation of pig organs in nonhuman primates - Xuan Zhang; Quancheng Wang; Jingjun Zhao; Xiao Li; Wei Peng; Zhaoxu Yang; Zhibin Lin; Long Yang; Rui Ding; Kaishan Tao; Kefeng Dou (Science China Life Sciences, 2021)

Community structure of bacterioplankton and its relationship with environmental factors in the upper reaches of the Heihe River in Qinghai Plateau - Zhang Qian‐Qian; Jian Sheng‐Long; Li Ke‐Mao; Wu Zhen‐Bing; Guan Hong‐Tao; Hao Jin‐Wen; Wang Shu‐Yi; Lin Yao‐Yao; Wang Guo‐Jie; Li Ai‐Hua (Environmental Microbiology, 2021)
Summary Planktonic microorganisms play a key role in the biogeochemical processes of the aquatic system, and they may be affected by many factors. High‐throughput sequencing technology was used in this study to investigate and study the bacterioplankton community of water bodies in the upper reaches of the Heihe River Basin in Qinghai Plateau. Results showed that Proteobacteria, Firmicutes, Bacteroidetes and Actinobacteria are the predominant phyla in this river section, while the main genera are Thiomonas , Acidibacillus , Acidocella , Rhodanobacter , Acidithiobacter and Gallionella , which are autochthonous in the acid‐mine drainage. Additionally, total nitrogen, total phosphorus, permanganate index and pH are significantly correlated with the bacterioplankton abundance and are the main limiting factors for the spatial distribution of the bacterioplankton. PICRUSt inferred that the mainstream microbial assemblages had a higher abundance of KOs belong to metabolism of terpenoids and polyketides, while the tributary had higher abundance of KOs belong to the immune system. The relationship between bacterioplankton community composition and environmental factors in the Heihe River basin was discussed for the first time in this study, which provides a theoretical basis for the healthy, orderly development of the water environment in the Heihe River Basin.

Long‐term active restoration of extremely degraded alpine grassland accelerated turnover and increased stability of soil carbon - Yanfu Bai; Lina Ma; Abraham A. Degen; Muhammad K. Rafiq; Yakov Kuzyakov; Jingxue Zhao; Rui Zhang; Tao Zhang; Wenyin Wang; Xiaogang Li; Ruijun Long; Zhanhuan Shang (Global Change Biology, 2020)
Soil nutrient contents and organic carbon (C) stability are key indicators for restoration of degraded grassland. However, the effects of long‐term active restoration of extremely degraded grassland on soil parameters have been equivocal. The aims of this study were to evaluate the impact of active restoration of degraded alpine grassland on: (a) soil organic matter (SOM) mineralization; and (b) the importance of biotic factors for temperature sensitivity ( Q 10 ) of SOM mineralization. Soils were sampled from intact, degraded and restored alpine grasslands at altitudes ranging between 3,900 and 4,200 m on the Tibetan Plateau. The samples were incubated at 5, 15 and 25°C, and Q 10 values of SOM mineralization were determined. Structural equation modeling was used to evaluate the importance of vegetation, soil physico‐chemical properties and microbial parameters for Q 10 regulation. The Q 10 of N mineralization was similar among intact, degraded and restored soils (0.84–1.24) and was higher in topsoil (1.09) than in subsoil (0.92). The best predictive factor of CO 2 ‐ Q 10 for intact grassland was microbial biomass, for degraded grassland was basal microbial respiration, and for restored grassland was soil bulk density. Restoration by planting vegetation decreased the Q 10 of SOM mineralization as soil bulk density, the most important negative predictor, increased in restored grassland. The Q 10 of SOM mineralization in topsoil was 14% higher than in subsoil because of higher microbial abundance and exo‐enzyme activities. The NH 4 + content was greatest in intact soil, while NO 3 − content was greatest in degraded soil. The SOM mineralization rate decreased with grassland degradation and increased after long‐term (>10 years) restoration. In conclusion, extremely degraded grassland needs proper long‐term management in active restoration projects, especially for improvement of soil nutrients in a harsh environment.

On the responses of soil layers surrounding a suction bucket under cyclic loads - Bin Zhang; Huan-long Kang; Xu-hui Zhang; Xiao-bing Lu; Yu-tao Li (Marine Georesources & Geotechnology, 2020)

Recent rainfall- and excavation-induced bedding rockslide occurring on 22 October 2018 along the Jian-En expressway, Hubei, China - Haibing Yu; Changdong Li; Jia-Qing Zhou; Wenqiang Chen; Jingjing Long; Xutao Wang; Tao Peng (Landslides, 2020)

Postchemotherapy hippocampal functional connectivity patterns in patients with breast cancer: a longitudinal resting state functional MR imaging study - Yun Feng; Dilihumaer Tuluhong; Zhao Shi; Li Juan Zheng; Tao Chen; Guang Ming Lu; Shaohua Wang; Long Jiang Zhang (Brain Imaging and Behavior, 2020)

Characterization of a Cu2+, SDS, alcohol and glucose tolerant GH1 β-glucosidase from Bacillus sp. CGMCC 1.16541 - Yi-Rui Yin; Peng Sang; Feng-Li Yang; Tao Li; Run-Feng Yang; Hong-Yan Liu; Zong-Long Luo; Wen-Jun Li; Li-Quan Yang (Antonie van Leeuwenhoek, 2020)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

Late Pleistocene environmental information on the Diexi paleo-dammed lake of the upper Minjiang River in the eastern margin of the Tibetan Plateau, China - Lan-sheng Wang; Xiao-qun Wang; Jun-hui Shen; Guan Yin; Jie Cui; Xiang-ning Xu; Zhi-long Zhang; Tao Wan; Li-wang Wen (Journal of Mountain Science, 2020)

Correction to: The Effects of 50 nm Unmodified Nano-ZnO on Lipid Metabolism and Semen Quality in Male Mice - Tao Kong; Shu-Hui Zhang; Cai Zhang; Ji-Liang Zhang; Fan Yang; Guo-Yong Wang; Zi-Jun Yang; Dong-Ying Bai; Yun-Yun Shi; Tian-Qi Liu; Hai-Long Li (Biological Trace Element Research, 2020)

The Effects of 50 nm Unmodified Nano-ZnO on Lipid Metabolism and Semen Quality in Male Mice - Tao Kong; Shu-Hui Zhang; Cai Zhang; Ji-Liang Zhang; Fan Yang; Guo-Yong Wang; Zi-Jun Yang; Dong-Ying Bai; Yun-Yun Shi; Tian-Qi Liu; Hai-Long Li (Biological Trace Element Research, 2020)

iTRAQ-based proteomic analysis of resistant Nicotiana tabacum in response to Bemisia tabaci infestation - Song-tao Zhang; Yue Long; Song-jie Zhang; Ning Li; De-xin Chen; Hong-fang Jia; Hong-ying Zhang; Yong-xia Yang (Arthropod-Plant Interactions, 2019)

Effect of Chronic Exposure to Methomyl on Tissue Damage and Apoptosis in Testis of Tilapia (Oreochromis niloticus) and Recovery Pattern - Shun Long Meng; Tao Liu; Xi Chen; Li Ping Qiu; Geng Dong Hu; Chao Song; LiMin Fan; Yao Zheng; Jia Zhang Chen; Pao Xu (Bulletin of Environmental Contamination and Toxicology, 2019)

Genomic and transcriptomic insights into the survival of the subaerial cyanobacterium Nostoc flagelliforme in arid and exposed habitats - Jin‐Long Shang; Min Chen; Shengwei Hou; Tao Li; Yi‐Wen Yang; Qi Li; Hai‐Bo Jiang; Guo‐Zheng Dai; Zhong‐Chun Zhang; Wolfgang R. Hess; Bao‐Sheng Qiu (Environmental Microbiology, 2019)
Summary The cyanobacterium Nostoc flagelliforme is an extremophile that thrives under extraordinary desiccation and ultraviolet (UV) radiation conditions. To investigate its survival strategies, we performed whole‐genome sequencing of N. flagelliforme CCNUN1 and transcriptional profiling of its field populations upon rehydration in BG11 medium. The genome of N. flagelliforme is 10.23 Mb in size and contains 10 825 predicted protein‐encoding genes, making it one of the largest complete genomes of cyanobacteria reported to date. Comparative genomics analysis among 20 cyanobacterial strains revealed that genes related to DNA replication, recombination and repair had disproportionately high contributions to the genome expansion. The ability of N. flagelliforme to thrive under extreme abiotic stresses is supported by the acquisition of genes involved in the protection of photosynthetic apparatus, the formation of monounsaturated fatty acids, responses to UV radiation, and a peculiar role of ornithine metabolism. Transcriptome analysis revealed a distinct acclimation strategy to rehydration, including the strong constitutive expression of genes encoding photosystem I assembly factors and the involvement of post‐transcriptional control mechanisms of photosynthetic resuscitation. Our results provide insights into the adaptive mechanisms of subaerial cyanobacteria in their harsh habitats and have important implications to understand the evolutionary transition of cyanobacteria from aquatic environments to terrestrial ecosystems.

Associations of HSP90AA2 gene polymorphisms with disease susceptibility, glucocorticoids efficacy and health-related quality of life in Chinese systemic lupus erythematosus patients - Man Zhang; Su-Su Li; Qiao-Mei Xie; Jian-Hua Xu; Xiu-Xiu Sun; Fa-Ming Pan; Sheng-Qian Xu; Sheng-Xiu Liu; Jin-Hui Tao; Shuang Liu; Jing Cai; Pei-Ling Chen; et al. (Genes & Genomics, 2018)

Update on the clinical application of deep brain stimulation in sleep dysfunction of Parkinson’s disease - Shuang Zou; Yu-Long Lan; Ya-Ping Hu; Xiao-Xue Yin; Wen-Long Liu; Tao Li; Zhanhua Liang (Acta Neurologica Belgica, 2018)

Numerical Simulation and Uncertainty Analysis of an Axial-Flow Waterjet Pump - Ji-Tao Qiu; Chen-Jun Yang; Xiao-Qian Dong; Zong-Long Wang; Wei Li; Francis Noblesse (Journal of Marine Science and Engineering, 2018)
Unsteady Reynolds-averaged Navier–Stokes simulations of an axial-flow pump for waterjet propulsion are carried out at model scale, and the numerical uncertainties are analyzed mainly according to the procedure recommended by the twenty-eighth International Towing Tank Conference. The two-layer realizable k-ε model is adopted for turbulence closure, and the flow in viscous sub-layer is resolved. The governing equations are discretized with second-order schemes in space and first-order scheme in time and solved by the semi-implicit method for pressure-linked equations. The computational domain is discretized into block-structured hexahedral cells. For an axial-flow pump consisting of a seven-bladed rotor and a nine-bladed stator, the uncertainty analysis is conducted by using three sets of successively refined grids and time steps. In terms of the head and power over a range of flow rates, it is verified that the simulation uncertainty is less than 4.3%, and the validation is successfully achieved at an uncertainty level of 4.4% except for the lowest flow rate. Besides this, the simulated flow features around rotor blade tips and between the stator and rotor blade rows are investigated.

Physicochemical Control of the Early Permian Xiangshan Fe-Ti Oxide Deposit in Eastern Tianshan (Xinjiang), NW China - Yu Shi; Yuwang Wang; Jingbin Wang; Lutong Zhao; Hongjing Xie; Lingli Long; Tao Zou; Dedong Li; Guochao Zhou (Journal of Earth Science, 2018)

Neuroprotective Effect and Mechanism of Action of Tetramethylpyrazine Nitrone for Ischemic Stroke Therapy - Gaoxiao Zhang; Tao Zhang; Liangmiao Wu; Xinhua Zhou; Jianbo Gu; Cuimei Li; Wei Liu; Cheng Long; Xifei Yang; Luchen Shan; Lipeng Xu; Yuqiang Wang; et al. (NeuroMolecular Medicine, 2018)

Effect of Electrospun Fibrous Scaffolds with Different Fiber Orientations on the Alignment of Microvessel-Like Structures - Zhenzhen Wu; Tao Yang; Chongyun Bao; Mingzheng Li; Hockin H. K. Xu; XueJuan Liao; Long Li; Ranran Huang; Jian Pan; Xian Liu (Journal of Medical and Biological Engineering, 2018)

Relationship Between Perisylvian Essential Language Sites and Arcuate Fasciculus in the Left Hemisphere of Healthy Adults - Yu Lin; Kai Zhang; Shuai Li; Song Li; Jingna Jin; Fang Jin; Wen Qin; Long Hai; Meng Zhu; Chunshui Yu; Zhipeng Liu; Tao Yin; et al. (Neuroscience Bulletin, 2017)

Low Serum Levels of Brain-Derived Neurotrophic Factor Were Associated with Poor Short-Term Functional Outcome and Mortality in Acute Ischemic Stroke - Jing Wang; Li Gao; Yan-Long Yang; Yu-Qian Li; Tao Chang; Ming-Hao Man; Xing-Ye Zhang; Shao-Chun Guo; Li-Hong Li (Molecular Neurobiology, 2017)

Rock strata movement and subsidence based on MDDA, an improved discontinuous deformation analysis method in mining engineering - Jian-ping Zuo; Yun-jiang Sun; Yue-chun Li; Jin-tao Wang; Xu Wei; Long Fan (Arabian Journal of Geosciences, 2017)

Novel adefovir mono L-amino acid ester, mono bile acid ester derivatives: Design, synthesis, biological evaluation, and molecular docking study - Ya Chen; Wen Zheng Zhang; Jing Li; Tao Xiao; Jiang Xia Liu; Min Luo; Hang Su; Xiao-Zhong Fu; Ting Liu; Yong-Xi Dong; Yong-Long Zhao; Bin He; et al. (Medicinal Chemistry Research, 2017)

Genetic diversity and population structure of the veined rapa whelk Rapana venosa along the coast of China based on microsatellites - Dong-Xiu Xue; Tao Zhang; Yu-Long Li; Jin-Xian Liu (Fisheries Science, 2017)

230Th/238U dating of hydrothermal sulfides from Duanqiao hydrothermal field, Southwest Indian Ridge - Weifang Yang; Chunhui Tao; Huaiming Li; Jin Liang; Shili Liao; Jiangping Long; Zhibang Ma; Lisheng Wang (Marine Geophysical Research, 2017)

Warm–cold colonization: response of oaks to uplift of the Himalaya–Hengduan Mountains - Hong‐Hu Meng; Tao Su; Xiao‐Yang Gao; Jie Li; Xiao‐Long Jiang; Hang Sun; Zhe‐Kun Zhou (Molecular Ecology, 2017)
Clarifying the relationship between distribution patterns of organisms and geological events is critical to understanding the impact of environmental changes on organismal evolution. Quercus sect. Heterobalanus is now distributed across the Himalaya–Hengduan Mountains ( HHM ) and warm lowland in East China, yet how the distribution patterns of this group changed in response to the HHM uplift remains largely unknown. This study examines the effect of tectonic events in the HHM region on the oaks, providing a biological perspective on the geological history of this region. Fifty‐six populations of Quercus sect. Heterobalanus were genotyped using four chloroplast DNA regions and nine nuclear simple sequence repeat loci to assess population structure and diversity, supplemented by molecular dating and ancestral area reconstructions. The underlying demographic dynamics were compared using ecological niche models of the species distributions during the last glacial maximum and the present. These analyses illustrate that Quercus sect. Heterobalanus diversified as the HHM uplifted and climatic cooling during the mid‐Miocene, colonizing the cold habitats from warm broadleaf mixed forests. Lineages in cold highlands and warm lowlands have diverged as a consequence of local adaptation to diverging climates since the late Miocene. Our results suggest that continuous uplift of the HHM in the late Miocene to early Pliocene accompanied by simultaneous cooling triggered the differentiation of oaks. The biogeography of Quercus sect. Heterobalanus illuminates the geological events responsible for the modern‐day HHM .

Developmental changes in digestive enzyme activity in American shad, Alosa sapidissima, during early ontogeny - Xiao-Qiang Gao; Zhi-Feng Liu; Chang-Tao Guan; Bin Huang; Ji-Lin Lei; Juan Li; Zheng-Long Guo; Yao-Hui Wang; Lei Hong (Fish Physiology and Biochemistry, 2017)

Thermoactivated persulfate oxidation of pesticide chlorpyrifos in aquatic system: kinetic and mechanistic investigations - Lei Zhou; Ya Zhang; Rongrong Ying; Guoqing Wang; Tao Long; Jianhua Li; Yusuo Lin (Environmental Science and Pollution Research, 2017)

Contrasting response of two grassland soils to N addition and moisture levels: N2O emission and functional gene abundance - Xi-En Long; Ju-Pei Shen; Jun-Tao Wang; Li-Mei Zhang; Hongjie Di; Ji-Zheng He (Journal of Soils and Sediments, 2017)

Biodegradation of the Herbicide 2,4-Dichlorophenoxyacetic Acid by a New Isolated Strain of Achromobacter sp. LZ35 - Zhen-Yuan Xia; Long Zhang; Yan Zhao; Xin Yan; Shun-Peng Li; Tao Gu; Jian-Dong Jiang (Current Microbiology, 2017)

Antioxidant Efficacy of Protein Hydrolysates from Large Yellow Croaker ( Pseudosciaena crocea ) in D-galactose-Induced Aging Mice - Chong Zhang; Ning Ning Zhang; Zhi Yu Li; Yu Ting Tian; Long Tao Zhang; Bao Dong Zheng (Journal of Aquatic Food Product Technology, 2017)

Genome-wide analysis of shoot growth-associated alternative splicing in moso bamboo - Long Li; Tao Hu; Xueping Li; Shaohua Mu; Zhanchao Cheng; Wei Ge; Jian Gao (Molecular Genetics and Genomics, 2016)

The formation and evolution of the Qiaojia pull-apart basin, North Xiaojiang Fault Zone, Southwest China - Tian-tao Li; Xiang-jun Pei; Run-qiu Huang; Long-de Jin (Journal of Mountain Science, 2016)

Genomic and physiological analysis reveals versatile metabolic capacity of deep-sea Photobacterium phosphoreum ANT-2200 - Sheng-Da Zhang; Claire-Lise Santini; Wei-Jia Zhang; Valérie Barbe; Sophie Mangenot; Charlotte Guyomar; Marc Garel; Hai-Tao Chen; Xue-Gong Li; Qun-Jian Yin; Yuan Zhao; Jean Armengaud; et al. (Extremophiles, 2016)

Procalcitonin Is a Stronger Predictor of Long-Term Functional Outcome and Mortality than High-Sensitivity C-Reactive Protein in Patients with Ischemic Stroke - Chao Wang; Li Gao; Zhi-Guo Zhang; Yu-Qian Li; Yan-Long Yang; Tao Chang; Long-Long Zheng; Xing-Ye Zhang; Ming-Hao Man; Li-Hong Li (Molecular Neurobiology, 2016)

High pH-induced flocculation of marine Chlorella sp. for biofuel production - Fangfang Yang; Wenzhou Xiang; Jiewei Fan; Hualian Wu; Tao Li; Lijuan Long (Journal of Applied Phycology, 2016)

The SIRT1 inhibitor, nicotinamide, inhibits hepatitis B virus replication in vitro and in vivo - Wan-Yu Li; Ji-Hua Ren; Na-Na Tao; Long-Kuan Ran; Xiang Chen; Hong-Zhong Zhou; Bo Liu; Xiao-Song Li; Ai-Long Huang; Juan Chen (Archives of Virology, 2016)

Spatial analysis of gastric cancer morbidity in regions of rapid urbanization: a case study in Xiamen, China - JiLai Liu; XinHu Li; Tao Lin; Long Dai; GuoQin Zhang; ChaoSheng Zhang; Hong Ye; Vee Gibson; QianJun Zhao (Stochastic Environmental Research and Risk Assessment, 2016)

Circadian variations in behaviors, BDNF and cell proliferation in depressive mice - Li-Tao Yi; Liu Luo; Yong-Jing Wu; Bin-Bin Liu; Xiao-Long Liu; Di Geng; Qing Liu (Metabolic Brain Disease, 2015)

Bergapten promotes bone marrow stromal cell differentiation into osteoblasts in vitro and in vivo - Ji-jie Xiao; Wen-ji Zhao; Xin-tao Zhang; Wen-long Zhao; Xiao-xia Wang; Shu-hui Yin; Fang Jiang; Yin-xia Zhao; Fang-ni Chen; Shao-lin Li (Molecular and Cellular Biochemistry, 2015)

Subcutaneous Injections of the Mannose-Sensitive Hemagglutination Pilus Strain of Pseudomonas aeruginosa Stimulate Host Immunity, Reduce Bladder Cancer Size and Improve Tumor Survival in Mice - Tao Li; Li Yang; Sheng-jun Fu; Er-long Xiao; Xuan Yuan; Jian-zhong Lu; Bao-liang Ma; Ting-kai Shi; Zhi-ping Wang (Cell Biochemistry and Biophysics, 2015)

Involvement of sulfhydryl compounds and antioxidant enzymes in H2S-induced heat tolerance in tobacco (Nicotiana tabacum L.) suspension-cultured cells - Zhong-Guang Li; Wei-Biao Long; Shi-Zhong Yang; Yang-Cai Wang; Ji-Hong Tang; Tao Chen (In Vitro Cellular & Developmental Biology - Plant, 2015)

Establishment and characterization of a gonad cell line from half-smooth tongue sole Cynoglossus semilaevis pseudomale - Ai Sun; Song-Lin Chen; Feng-Tao Gao; Hai-Long Li; Xiao-Feng Liu; Na Wang; Zhen-Xia Sha (Fish Physiology and Biochemistry, 2015)

Bioaccessibility and health risk of heavy metals in ash from the incineration of different e-waste residues - Xiao-Qing Tao; Dong-Sheng Shen; Jia-Li Shentu; Yu-Yang Long; Yi-Jian Feng; Chen-Chao Shen (Environmental Science and Pollution Research, 2015)

7-Chlorokynurenic acid (7-CTKA) produces rapid antidepressant-like effects: through regulating hippocampal microRNA expressions involved in TrkB-ERK/Akt signaling pathways in mice exposed to chronic unpredictable mild stress - Bin-Bin Liu; Liu Luo; Xiao-Long Liu; Di Geng; Qing Liu; Li-Tao Yi (Psychopharmacology, 2015)

Prognostic Value of Mannose-Binding Lectin: 90-Day Outcome in Patients with Acute Ischemic Stroke - Zhi-Guo Zhang; Chao Wang; Jing Wang; Zhuo Zhang; Yan-Long Yang; Li Gao; Xing-Ye Zhang; Tao Chang; Guo-Dong Gao; Li-Hong Li (Molecular Neurobiology, 2015)

Calcitonin Gene-Related Peptide Inhibits Osteolytic Factors Induced by Osteoblast In Co-Culture System with Breast Cancer - Hui Zhao; Lin-lin Ning; Zhi-yu Wang; Hong-tao Li; Dan Qiao; Yang Yao; Huan-long Qin (Cell Biochemistry and Biophysics, 2014)

Down-regulation of Gli-1 inhibits hepatocellular carcinoma cell migration and invasion - Jing-Song Chen; Hua-Shu Li; Jiong-Qiang Huang; Long-Juan Zhang; Xi-Lin Chen; Qian Wang; Jian Lei; Ju-Tao Feng; Qin Liu; Xiao-Hui Huang (Molecular and Cellular Biochemistry, 2014)

Pharmacokinetics study of asperosaponin VI and its metabolites cauloside A, HN saponin F and hederagenin - Er-Wei Liu; Jia-Long Wang; Li-Feng Han; Yan-Xu Chang; Tao Wang; Yan Huo; Lei Wang; Xiu-Mei Gao (Journal of Natural Medicines, 2014)

Supramolecular Interaction of Two Tryptophans with p-sulfonated calix[4,6,8]arene - Tao-Tao Pang; Hai-Long Liu; Li-Ming Du; Yin-Xia Chang; Yun-Long Fu (Journal of Fluorescence, 2014)

Lipopolysaccharides Reduce Adipogenesis in 3T3-L1 Adipocytes Through Activation of NF-κB Pathway and Downregulation of AMPK Expression - Lifeng Wang; Linlin Li; Xinjian Ran; Mei Long; Minfang Zhang; Yicun Tao; Xin Luo; Ye Wang; Yi Jiao; Xinmin Mao; Jun Ren (Cardiovascular Toxicology, 2013)

Improvement of fluorescent chromosome in situ PCR and its application in the phylogeny of the genus Fagopyrum Mill. using nuclear genes of chloroplast origin (cpDNA) - Fen-Long Li; Friedrich J. Zeller; Kai-Feng Huang; Tao-Xiong Shi; Qing-Fu Chen (Plant Systematics and Evolution, 2013)

Using proteomic analysis to find the proteins involved in resistance against Sclerotinia sclerotiorum in adult Brassica napus - Li Wen; Tai-Long Tan; Jia-Bin Shu; Ying Chen; Ying Liu; Zhong-Fang Yang; Qiu-Ping Zhang; Ming-Zhi Yin; Jun Tao; Chun-Yun Guan (European Journal of Plant Pathology, 2013)

Quantitative trait loci for grain-quality traits across a rice F2 population and backcross inbred lines - Bingyue Lu; Chunyan Yang; Kun Xie; Long Zhang; Tao Wu; Linfang Li; Xi Liu; Ling Jiang; Jianmin Wan (Euphytica, 2013)

Changes in the BAG1 Expression of Schwann Cells After Sciatic Nerve Crush - Hao Wu; Yonghua Liu; Yuan Zhou; Long Long; Xinghai Cheng; Lei Ji; Hai Weng; Tao Ding; Jiao Yang; Haixiang Wei; Ming Li; Weipeng Huan; et al. (Journal of Molecular Neuroscience, 2013)

Temporal and Spatial Expression of KIF3B after Acute Spinal Cord Injury in Adult Rats - Xiaowei Yu; Hai Wen; Jianhua Cao; Binbin Sun; Tao Ding; Ming Li; Hao Wu; Long Long; Xinghai Cheng; Guangfei Xu; Feng Zhang (Journal of Molecular Neuroscience, 2013)

Dynamic expression of small RNA populations in larch (Larix leptolepis) - Junhong Zhang; Tao Wu; Long Li; Suying Han; Xinmin Li; Shougong Zhang; Liwang Qi (Planta, 2013)

Molecular Cloning and Characterization of Two 9-Lipoxygenase Genes from Taxus chinensis - Shu-tao Li; Meng Zhang; Chun-hua Fu; Sha Xie; Yu Zhang; Long-jiang Yu (Plant Molecular Biology Reporter, 2012)

Enhancing Taxol Biosynthesis by Overexpressing a 9-Cis-Epoxycarotenoid Dioxygenase Gene in Transgenic Cell Lines of Taxus chinensis - Shu-tao Li; Chun-hua Fu; Meng Zhang; Yu Zhang; Sha Xie; Long-jiang Yu (Plant Molecular Biology Reporter, 2012)

Effects of indole-3-acetic acid and auxin transport inhibitors on the style curvature of three Alpinia species (Zingiberaceae) - Yin-Ling Luo; Ting-Ju Bi; Dong Li; Zhi-Long Su; Chuan Tao; Yan-Jiang Luo; Qing-Jun Li (Acta Physiologiae Plantarum, 2012)

C/EBP-α ameliorates CCl4-induced liver fibrosis in mice through promoting apoptosis of hepatic stellate cells with little apoptotic effect on hepatocytes in vitro and in vivo - Li-Li Tao; Yuan-Yuan Cheng; Di Ding; Shuang Mei; Jia-Wen Xu; Juan Yu; Qi Ou-Yang; Long Deng; Qi Chen; Qing-Quan Li; Zu-De Xu; Xiu-Ping Liu (Apoptosis, 2012)

SIRT1 is required for long-term growth of human mesenchymal stem cells - Hong-Feng Yuan; Chao Zhai; Xin-Long Yan; Dan-Dan Zhao; Jing-Xue Wang; Quan Zeng; Lin Chen; Xue Nan; Li-Juan He; Si-Ting Li; Wen Yue; Xue-Tao Pei (Journal of Molecular Medicine, 2012)

Induction of Mitogynogenetic Diploids and Identification of WW Super-female Using Sex-Specific SSR Markers in Half-Smooth Tongue Sole (Cynoglossus semilaevis) - Song-Lin Chen; Xiang-Shan Ji; Chang-Wei Shao; Wen-Long Li; Jing-Feng Yang; Zuo Liang; Xiao-Lin Liao; Gen-Bo Xu; Ying Xu; Wen-Tao Song (Marine Biotechnology, 2012)

Overexpression of a 10-deacetylbaccatin III-10 β-O-acetyltransferase gene leads to increased taxol yield in cells of Taxus chinensis - Peng Zhang; Shu-Tao Li; Ting-Ting Liu; Chun-Hua Fu; Peng-Peng Zhou; Chun-Fang Zhao; Long-Jiang Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Agrobacterium tumefaciens-mediated Transformation of A Taxol-Producing Endophytic Fungus, Cladosporium cladosporioides MD2 - Peng Zhang; Ting-Ting Liu; Peng-Peng Zhou; Shu-Tao Li; Long-Jiang Yu (Current Microbiology, 2011)

Effects of oriented substrates on cell morphology, the cell cycle, and the cytoskeleton in Ros 17/2.8 cells - Hong Li; Juan Chen; Yan Zhang; ShuJin Sun; ZuLai Tao; Mian Long (Science China Life Sciences, 2010)

Effects of intercropping and Rhizobium inoculation on yield and rhizosphere bacterial community of faba bean (Vicia faba L.) - Nan Nan Zhang; Yan Mei Sun; Long Li; En Tao Wang; Wen Xin Chen; Hong Li Yuan (Biology and Fertility of Soils, 2010)

Testicular toxicity induced by dietary cadmium in cocks and ameliorative effect by selenium - Jin-Long Li; Rui Gao; Shu Li; Jin-Tao Wang; Zhao-Xin Tang; Shi-Wen Xu (BioMetals, 2010)

Growth factors induce the improved cardiac remodeling in autologous mesenchymal stem cell-implanted failing rat hearts - Ze-wei Tao; Long-gui Li; Zhao-hua Geng; Tao Dang; Shan-jun Zhu (Journal of Zhejiang University-SCIENCE B, 2010)

Novel microRNAs uncovered by deep sequencing of small RNA transcriptomes in bread wheat (Triticum aestivum L.) and Brachypodium distachyon (L.) Beauv - Bo Wei; Tao Cai; Rongzhi Zhang; Aili Li; Naxin Huo; Shan Li; Yong Q. Gu; John Vogel; Jizeng Jia; Yijun Qi; Long Mao (Functional & Integrative Genomics, 2009)

Improvement of arachidonic acid and eicosapentaenoic acid production by increasing the copy number of the genes encoding fatty acid desaturase and elongase into Pichia pastoris - Yun-Tao Li; Mao-Teng Li; Chu-Hua Fu; Peng-Peng Zhou; Jian-Min Liu; Long-Jiang Yu (Biotechnology Letters, 2009)

Molecular cytogenetic characterization of wheat–Secale africanum amphiploids and derived introgression lines with stripe rust resistance - Zu-Jun Yang; Guang-Rong Li; Ju-Qing Jia; Xue Zeng; Meng-Ping Lei; Zi-Xian Zeng; Tao Zhang; Zheng-Long Ren (Euphytica, 2009)

Transformation of sugarcane with ACC oxidase antisense gene - Ai-Qin Wang; Wei-Qing Dong; Yuan-Wen Wei; Cheng-Mei Huang; Long-Fei He; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2009)

Identification of α-gliadin genes in Dasypyrum in relation to evolution and breeding - Guang-Rong Li; Cheng Liu; Zi-Xian Zeng; Ju-Qing Jia; Tao Zhang; Jian-Ping Zhou; Zheng-Long Ren; Zu-Jun Yang (Euphytica, 2009)

Variation of 423G>T in the Agouti Gene Exon 4 in Indigenous Chinese Goat Breeds - Chun-Juan Tang; Rong-Yan Zhou; Xiang-Long Li; Jing-Wen Zhao; Lan-Hui Li; Fu-Jun Feng; Dong-Feng Li; Jian-Tao Wang; Xiu-Li Guo; Jing-Fen Keng (Biochemical Genetics, 2008)

Molecular cloning and tissue specific expression of an elongation factor 1A gene in sugarcane stalks - Ai-Qin Wang; Ying-Zhi Qin; Xing-Zhi Ye; Ye-Geng Fan; Long-Fei He; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2008)

Cell therapy in congestive heart failure - Ze-wei Tao; Long-gui Li (Journal of Zhejiang University-SCIENCE B, 2007)

Cloning of three members of acc synthase gene family in sugarcane - Ai-Qin Wang; Li-Tao Yang; Zi-Zhang Wang; Yu-Tuo Wei; Long-Fei He; Yang-Rui Li (Sugar Tech, 2006)

Copper Speciation and Accumulation in the Gill Microenvironment of Carp (Cyprinus carpio) in the Presence of Kaolin Particles - S. Tao; A. Long; R. W. Dawson; F. Xu; B. Li; J. Cao; J. Fang (Archives of Environmental Contamination and Toxicology, 2002)